Synthesis and in-depth characterization of hydrochars derived from cellulose and nanocellulose - Antônio J.R. Castro; Gilberto D. Saraiva; Franciso H. Soares Junior; Alessandra A. Aquino; Laís H.S. Vieira; Rai F. Jucá; Cristiane Spagnol; Adley F. Rubira; Antonio G. Souza Filho; Odair P. Ferreira (Biomass and Bioenergy, 2027)

Ecological and economic outcomes of area-based conservation and sustainable fisheries management in the Mediterranean Sea - M. D. Castro-Cadenas; J. Claudet; M. Ortega; V. Sbragaglia; M. Coll (Reviews in Fish Biology and Fisheries, 2026)
Intergovernmental targets are reinforcing the need for more sustainable fisheries and more effective marine conservation. It is now urgent to understand how area-based conservation and sustainable fisheries management tools contribute to these environmental and socio-economic goals. Here, we systematically reviewed and assessed the outcomes of marine protected areas (accounting for their level of protection and of enforcement), fisheries restricted areas, and fishing effort reduction measures in the Mediterranean Sea, using 11 ecological and economic indicators. We show that commercial species in general, and fish species in particular, showed the highest proportion of positive to neutral effects in response to the management tools assessed compared to non-commercial and benthic assemblages. Among the management tools, partially protected areas showed the lowest proportion of positive to neutral effects compared to fully protected areas, and to the other management tools. Partially protected areas and fully protected areas showed higher neutral to negative ratio than fishing effort reduction measures overall. Within MPA protection levels with high enforcement, fully protected areas outperformed minimally protected areas, based on the higher positive to neutral effects ratio. Our results further underscored the critical role of enforcement, particularly for fully protected areas, which were found more beneficial overall under high enforcement than medium enforcement (based on positive to neutral effects ratio). Our findings support the prioritisation of well enforced fully protected areas and the integration of fisheries management and conservation objectives in marine spatial planning to effectively achieve regional and global sustainability goals for the ocean.

Multitargeted metabarcoding and morphological identification reveal practice-specific soil biodiversity outcomes in Mediterranean cropping systems - Lur Epelde; Ninon Delcourt; Jérôme Cortet; Anders Lanzén; Carlos Garbisu; José Luis Lavín; Luigi P. D'Acqui; Sara Di Lonardo; Martina Grattacaso; Eliana L. Tassi; Fatima-Zahraa El Balghiti; Leila Benidire; et al. (Soil Biology and Biochemistry, 2026)

Chemical composition of fine particulate matter and all-cause mortality of older lung cancer patients - Yaguang Wei; Jiaowei Gong; Edgar Castro; Min Zhang; Robert O. Wright; Christine C. Ekenga; Joel D. Schwartz (Environmental Research, 2026)

Photocatalytic caffeine degradation and toxicity reduction using reduced graphene oxide-modified zinc telluride - A. J. Vilvert; P. D. Macruz; R. P. Nippes; H. C. L. Geraldino; L. V. de Castro-Hoshino; I. R. Bautitz; J. C. G. Moraes (International Journal of Environmental Science and Technology, 2026)
The occurrence of emerging pollutants in aquatic matrices has raised environmental concern because of their persistence and potential toxicity. This study assessed caffeine degradation and toxicity reduction using zinc telluride functionalized with reduced graphene oxide as heterogeneous photocatalyst. The catalysts were synthesized by the wet impregnation method with excess solvent, and characterized by physicochemical and optical techniques. The results indicated zinc telluride nanoparticles distributed on the surface of reduced graphene oxide sheets, together with changes in textural and optical properties, including a lower band gap for the composites. Photocatalytic tests were performed using a mercury vapor lamp emitting ultraviolet–visible radiation, with the main emission at 365 nm. The effects of reduced graphene oxide content, catalyst loading, initial caffeine concentration, and pH variation were evaluated. Under the tested experimental conditions, the composite containing 1.0% reduced graphene oxide showed the highest degradation performance, reaching 93% caffeine degradation in 85 min. The degradation profile was best described by the half-order kinetic model. The reduced photoluminescence intensity suggests lower electron–hole recombination, although direct confirmation of reactive species requires complementary analyses. Toxicity tests indicated lower Artemia salina mortality and improved Lactuca sativa germination after treatment with the 1.0% reduced graphene oxide-modified zinc telluride catalyst. The results indicate that reduced graphene oxide incorporation can improve caffeine photodegradation and reduce toxicity under the evaluated conditions.

Evaluation of water quality from tubular wells in Brazil - G. G. O. de Souza; J. W. G. Castro; R. S. da Cadorso; E. M. de Lima; J. F. L. de Pereira; M. P. da Silva; Y. T. C. da Santos; F. G. Rodriguês; J. G. M. da Costa; H. D. M. Coutinho; G. B. Brito (International Journal of Energy and Water Resources, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Medicinal plant discrimination in Paramos and cloud forests of northern Peru: A study of deep learning techniques and a novel approach for data augmentation - W. Castro; M. Juarez; D. Gálvez-Paucar; V. Tirado; J. Gonzáles; F. Torres-Guevara (Remote Sensing Applications: Society and Environment, 2026)

Mn/Co-modified CaO pellets bound with mesoporous γ-Al2O3 for thermochemical energy storage: balancing energy-storage density, mechanical strength and solar absorptance - D. Castro-Yáñez; A. Peral; J. González-Aguilar; M. Romero; E.S. Sanz-Pérez; L. Briones; J.M. Escola (Journal of Cleaner Production, 2026)

On the Possibility of Ionospheric Memory Over the Low-Latitude Mexican Region - M. A. Sergeeva; I. D. Orrala-Legorreta; E. Rodriguez-Orozco; J. H. Castro-Chacon; O. A. Maltseva; J. A. Gonzalez-Esparza; P. Corona-Romero; V. J. Gatica-Acevedo; M. Pazos; M. E. Gonzalez-Alvarez; R. Bonifaz; A. Melgarejo-Morales; et al. (Pure and Applied Geophysics, 2026)
Features of possible regional ionospheric memory manifested themselves at low-latitudes under solar eclipse conditions.

A climate services organization supporting coastal resilience: lessons from the Stone Living Lab - K. A. Dafforn; M. Borrelli; K. Bosma; J. E. K. Byrnes; L. Castro-Diaz; R. F. Chen; J. Christo; D. Cook; F. Peri; R. Shoer; M. Albert; K. Bradley; et al. (Climatic Change, 2026)
There is a growing recognition that effective climate adaptation requires organizations that can translate science into policy-relevant, place-based implementation. The Stone Living Lab (SLL) was established as a climate services organization to help bridge the gap between climate adaptation research and real-world application. In this paper, we present the Lab as a model for how universities and NGOs can partner with government agencies, Indigenous groups, and local communities to strengthen coastal resilience, highlighting the structures, guiding principles and lessons learned over the last five years. Four guiding principles shape and distinguish the Lab’s approach, extending beyond the traditional focus on science and engineering research to also include climate preparedness, education and outreach and policy engagement. These principles continue to evolve in response to experience, particularly in navigating complex partnerships and engaging with stakeholder networks, which require sustained coordination, clear communication, and intentional alignment of roles, expectations, and timelines. Other lessons highlight the importance of visible, place-based solutions, knowledge sharing and maintaining a clear mission focus while balancing short-term outcomes with long-term resilience goals. Our aim here is to provide practical insights for researchers, practitioners and managers seeking to design or strengthen similar climate services organizations.

Non‐Stationary Dry‐Spell Hazard Probabilities for Spain - S. M. Vicente‐Serrano; S. Beguería; A. Royo; A. El Kenawy; M. Franquesa; A. Halifa‐Marin; M. Adell‐Michavila; A. Crespillo; D. Pérez‐Pajuelo; F. Domínguez‐Castro; C. Azorin‐Molina; L. Gimeno; et al. (International Journal of Climatology, 2026)
This study provides a comprehensive assessment of long‐term changes in dry‐spell dynamics across Spain for the period 1961–2024, using both classical non‐parametric methods and a novel non‐stationary probabilistic framework applied to exceedance series of dry‐spell durations. Using daily precipitation data from a dense network of quality‐controlled stations, dry‐spells were identified based on four thresholds (0.1, 1, 5, and 10 mm) to characterize their duration statistics, and generalized Pareto distributions (GPDs) were fitted under both stationary and non‐stationary specifications. A systematic percentile‐based evaluation was performed to determine optimal exceedance thresholds, and a bootstrap‐based significance test was applied to compare stationary and non‐stationary return levels. Complementary analyses examined trends in annual frequency, mean duration, and maximum dry‐spell length. Results consistently reveal that dry‐spell behaviour across Spain is dominantly stationary. Only a very small fraction of stations show significant non‐stationary effects in the GPD location parameter, whereas non‐stationary scale, shape, or full‐parameter models provide no robust improvement and introduce substantial uncertainty. Traditional trend analyses corroborate this finding: most stations (> 70%–85%, depending on threshold) exhibit no statistically significant changes in dry‐spell frequency, mean duration, or maximum duration. Spatial patterns of change are weak, and return levels associated with long recurrence periods (e.g., 50 years) remain highly stable throughout 1961–2024. Overall, these results support long‐term stationarity in the probability of extreme dry‐spells across Spain.

Bedinvetmab, alone or in combination with photobiomodulation and pulsed electromagnetic field therapy, on pain and quality of life in dogs with hip osteoarthritis - Letícia Orthey Cidral; Gilberto Serighelli-Júnior; Soraia Figueiredo de Souza; Ricardo Guilherme D’Otaviano de Castro Vilani (Veterinary Research Communications, 2026)
Osteoarthritis (OA) is one of the main causes of chronic pain in dogs, significantly impairing mobility and quality of life. This study aimed to evaluate the analgesic efficacy of bedinvetmab, administered alone and in combination with physiotherapy using photobiomodulation (PBM) and pulsed electromagnetic field therapy (PEMF), in dogs with hip OA. This was a prospective, randomized, comparative effectiveness trial involving 30 dogs allocated into two groups: BPG (bedinvetmab + physiotherapy) and BG (bedinvetmab). In the BPG, physiotherapy sessions were performed twice a week throughout the 90-day protocol. Pain was assessed through algometry and the Canine Brief Pain Inventory (CBPI) completed by the owners. Both groups showed significant clinical improvement ( p < 0.001). In the CBPI, both the Pain Severity Score (PSS) and Pain Interference Score (PIS) decreased significantly from baseline to day 90 in both groups. In algometry, the BPG showed a significant increase in pain threshold as early as day 15 (D15) and was superior to the BG from day 30 (D30; p = 0.027), with more pronounced differences at days 60, 75, and 90 (D60, D75, and D90; p < 0.001). These findings provide preliminary evidence that the combination of bedinvetmab and physiotherapy enhances pain control and promotes better quality of life in dogs with OA.

Lab-on-a-chip-compatible graphene oxide coatings via SAW atomization for supporting cell proliferation - Olga V. Balachova; Andrea C. Dorion Rodas; Sergey M. Balashov; Daniel D. da Purificação; Luciana D. Trino Albano; Caio C. de Lima Silva; Gabriel C. Kokkonias e Castro; Juliana K. M. Barboza Daguano (In vitro models, 2026)

Formulation and evaluation of a functional beverage from Ilex guayusa Loes. (Aquifoliaceae): Chemical analysis, antioxidant activity, and sensory acceptance - Luis G. Sequeda-Castañeda; Laura D. Bermeo-Pulido; Yineth Piñeros-Castro; Geison M. Costa; Yuri M. Castillo-Quiroga (Food and Humanity, 2026)

Unstable bridges—exploring the possibilities for “in between” spaces amidst divergent narratives in environmental governance - Blanca González-Mon; Violeta Cabello; Amanda Jiménez-Aceituno; María Mancilla García; Antonio J. Castro; María D. López-Rodríguez; Michele-Lee Moore; Maja Schlüter (Sustainability Science, 2026)
Social-ecological systems increasingly face polarization dynamics that challenge environmental governance. Such polarization implies the development of opposing narratives with limited interaction, each framing environmental problems and solutions in distinct ways. In this study, we analyze a case of narrative polarization around the eutrophication crises of the Mar Menor lagoon in Spain, focusing on how proposed solutions are narrated to address this complex environmental puzzle. We use a mixed-method approach that combines social network analysis and an analysis of narrative practices in interview situations, to investigate whether and how potential solutions to eutrophication in the Mar Menor can be understood as bridging spaces that create opportunities for interaction between divergent societal narratives. Our three-step analysis includes: (a) a network analysis of reports proposing solutions to identify solutions with a bridging role (i.e., those linking reports that otherwise have little overlap in the solutions proposed); (b) a thematic narrative analysis to investigate the solutions proposed by diverse actors; and (c) an analysis of narrative practices around selected bridging solutions to explore if they constitute new spaces where narratives can interact and confront positions - what we call bridging spaces. We suggest this mixed methods approach allows for the identification of potential bridging spaces to mediate polarization and outline directions for future research on both the case study specifically, and on polarization in environmental governance more generally.

Influence of pH and nitrogen source on metabolism and extracellular polymeric substance production in a mixed aerobic methanotrophic community - D. Primo-Catalunya; M.I. Peña-Castro; A. Sánchez-Melsió; J.L. Balcázar; M. Pijuan (Journal of Environmental Chemical Engineering, 2026)

Evolution of the primary productivity recovery at the Cretaceous-Paleogene boundary at the Caravaca distal section (Spain) - Claudia Sosa-Montes de Oca; Marta Rodrigo-Gámiz; Gines A. de Gea; Cristina Sequero; Yiming Zhang; Panteleimon Prokopiou; José Manuel Castro; Mª. Luisa Quijano; Richard D. Pancost (Global and Planetary Change, 2026)

Accuracy of blind approach and ultrasound–guided techniques for pudendal nerve block in cadaveric cats - a pilot study - Mariana Melânia Cristofolini; Henrique Zem Chequin Sprengel; Julia Milczewski Vilani; Viviane Luize Bosak; Marcello Machado; Ricardo Guilherme D’Otaviano de Castro Vilani (Veterinary Research Communications, 2026)
This blinded, randomized and prospective cadaveric pilot study compared the accuracy of a blind approach for pudendal nerve block (PNB–B) with that of the ultrasound–guided technique (PNB–US) in cats. Two male cat cadavers were used for a preliminary anatomical study to identify palpable bony landmarks, while eight additional cadavers were employed for the experimental phase. Each hemipelvis was randomly assigned to one of the two techniques: PNB–US, performed according to the deep dorsolateral method described by Adami et al. (J Feline Med Surg 15:901–907, 2013), or the PNB–B, developed based on the preliminary anatomical findings, identifying the application point laterally to the sacrococcygeal joint. Block accuracy was assessed by dye spread, considering the nerve branches stained in each approach. The success rate was 87.5% (7/8) for PNB–B and 75% (6/8) for PNB–US. In the injections considered accurate in PNB–B, dye was deposited at the point of confluence of sacral nerve branches forming the pudendal nerve, while in PNB–US the pudendal nerve was stained near the exit of the pelvis. The ischial nerve was inadvertently stained in 75% (6/8) of PNB–B and 25% (2/8) of PNB–US injections. These findings indicate that PNB–B can be considered an effective alternative to the ultrasound–guided technique, although, in clinical settings, it may produce motor blockade due to unintended ischial nerve involvement. The results provide preliminary data to support future in vivo clinical studies aimed at confirming the safety and analgesic efficacy of this novel blind technique in cats.

Consistent topsoil carbon density and driving factors in urban greenspaces and natural ecosystems - Beatriz Jiménez-Prieto; Pablo García-Palacios; Carmen Lorenzo-Rodríguez; Elena Aguilar-Santana; Josu G. Alday; Camelia Algora; Cristian Carrillo-Guzmán; Cristina Armas; Felipe Bastida; Leonor Calvo; María D. Carmona-Yáñez; Axel Campos-Castro; et al. (Plant and Soil, 2026)
Background Urban greenspaces have the potential to mitigate urban carbon footprints by storing soil organic carbon (SOC). Different management and plant communities associated with different types of urban greenspaces may hold contrasting SOC, as well as different proportions of particulate (POC) and mineral-associated organic carbon (MAOC). In addition, management could outweigh the effects of climate or soil properties as drivers of urban SOC storage, in contrast with natural environments. Methods We analyzed SOC, POC and MAOC densities (kg m −2 ) in topsoil (0-10 cm) across 27 cities in the Iberian Peninsula with contrasting climatic and edaphic conditions. At each city, we compared four types of urban greenspaces (golf courses, roundabouts, urban farms, and parks) with a nearby natural ecosystem. Results Results revealed that, despite large differences in their typology, contrasting urban greenspaces stored comparable topsoil SOC and MAOC densities to natural ecosystems. Golf courses and urban farms also showed similar POC density to natural ecosystems, whereas parks and roundabouts had lower amounts of this carbon fraction. Consistent with global natural patterns, MAOC dominated over POC in the topsoil, and both carbon fractions showed an inverse correlation with mean annual temperature. While MAOC exhibited saturation at higher SOC levels, POC steadily increased. Conclusion Although urban greenspaces are usually neglected in global soil carbon assessments, our study shows that, compared to natural ecosystems (median: 2.42 kg m −2 ; interquartile range: 1.77), these areas store an equally important density of carbon in the topsoil (median: 2.26 kg m −2 ; interquartile range: 1.30), and this carbon exhibits similar fraction dominance, temperature influence, and saturation across large spatial gradients.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Treatment of supravalvular mitral stenosis in a kitten with hybrid balloon angioplasty - R.L. Winter; D.M. Tillson; K.L. Maneval; M. Rajeev; D. Castro (Journal of Veterinary Cardiology, 2026)

Spatio-temporal performance of 2D local inertial hydrodynamic models for urban drainage and dam-break applications - Marcus N. Gomes Jr.; Maria A.R.A. Castro; Luis M.R. Castillo; Mateo H. Sánchez; Marcio H. Giacomoni; Rodrigo C.D. de Paiva; Paul D. Bates (Journal of Hydrology, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

The effect of transporting hitchhikers on the stability of loaded leaf-cutting ants - Alejandro G. Farji-Brener; Gleydson E. Silva; Amanda A. Bernardes; Beatriz D. Castro; Sofia T. B. Lima; Bianca dos Santos Neves (Insectes Sociaux, 2026)

Replacing natural savannas with eucalyptus and soybeans changes the matrix use and reduces bat taxonomic and functional diversity in the Amazonian savannas - Bruna S. Xavier; Karen Mustin; Tiago M. Marques; Marcelo M. Ferreira; Renato R. Hilário; José J. Toledo; Isaí J. Castro; Jorge M. Palmeirim; Ana M.C. Santos; Marcus V. Vieira; William D. Carvalho (Agriculture, Ecosystems & Environment, 2026)

Water security and hydrosocial resilience in the Peruvian Andes: Remote sensing and cultural governance in the Razuhuillca watershed - Bruno Kadafi Cardenas Morales; Yirme Yohu Gomez-Ccochachi; Nidia Leidy Quispe Godoy; Saríah Fanny Oré Gálvez; Walter Victor Castro Aponte; Jaqueline Chuquillanqui Gomez; Freddy Grover Rivera Garamendi; Solón Dante Carhuallanqui Ibarra; Santos Clemente Herrera Díaz; Crispin H.W. Barnes; Alexander D. Hernández-Nieves; Luis De Los Santos Valladares (Remote Sensing Applications: Society and Environment, 2026)

The ornithine-arginine cycle supported a toxic, metalimnic Planktothrix rubescens bloom - Brittany N. Zepernick; David J. Niknejad; Emily E. Chase; Blessing A. Abiodun; Meaghan J. Adler; Katelyn A. Houghton; Jason L. Olavesen; Qudus Sarumi; Alexander R. Truchon; Jillian L. Walton; Jack H. Cheshire; Keara Stanislawczyk; et al. (Harmful Algae, 2026)

Immediate and delayed biotic and environmental responses to the carbon cycle perturbation at the onset of OAE 1a – Insights from a new high-resolution record from the Western Tethys - Cristina Sequero; Sandro Froehner; José Manuel Castro; Ginés A. De Gea; María Luisa Quijano; B. David A. Naafs; Richard D. Pancost (Global and Planetary Change, 2026)

Drivers of seedling emergence and early growth of 12 European oak species: Results from a cross-continental experiment - Alexandro B. Leverkus; María Medina; Alba Lázaro-González; Laura Levy; Olivia Lorente-Casalini; Marino P. Reyes Martín; Enrique Andivia; Alessandro Bizzarri; Henrik Böhlenius; Vito E. Cambria; Claudia Cocozza; Branislav Cvjetković; et al. (Forest Ecology and Management, 2026)

Replacing the natural savanna matrix with eucalyptus plantations and soybean fields changes the seed rain promoted by bats in Amazonian savannas - Bruna S. Xavier; Jeferson Vizentin-Bugoni; Marcelo M. Ferreira; Tiago M. Marques; Renato R. Hilário; José J. Toledo; Isaí J. Castro; Karen Mustin; Jorge M. Palmeirim; Marcus V. Vieira; William D. Carvalho (Biological Conservation, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Under pressure: mapping the distribution of medically important Tityus Koch, 1836 (Buthidae) scorpions in Brazil using a century of Instituto Butantan records - Paulo A.M. Goldoni; Antonio D. Brescovit; Rodrigo A. Castro-Souza; Juliana Cequinel; Emanuel Marques-da-Silva; Luiz F.M. Iniesta (Toxicon, 2025)

Reproductive success over Calliandra fasciculata Benth. floral anthesis: evidence of adaptive generalization - Rodrigo Santiago; Pedro J. Bergamo; Vinícius L.G. Brito; Marsal D. Amorim; Lucas B. Castro; Sabrina A. Lopes; Cinthia S. Novaes; Larissa C. Mendes; Gizele C.A. Silva; Danila M. Silva; Ilmara A.O. Ferreira; Bernardo O. Dias; et al. (Flora, 2025)

Andrographolide increases adult hippocampal neurogenesis and prolongs contextual fear memory - Laura F. Jaimes; Matheus C. Passos; Lara M. Z. Mansk; Caio M. de Castro; Julián T. F. Vega; Leonardo de O. Guarnieri; Flávio A. G. Mourão; Alexander Birbrair; Victor R. Santos; Márcio F. D. Moraes; Grace S. Pereira (Psychopharmacology, 2025)

Developing science-informed maps and climate service for extreme rainfall in Spain - S. M. Vicente-Serrano; S. Beguería; F. Reig; A. Royo; M. Arretxea; M. Gil; B. Latorre; A. El Kenawy; M. Franquesa; A. Halifa-Marin; M. Adell-Michavila; A. Crespillo; et al. (Natural Hazards, 2025)
This study introduces the first high-resolution hazard probability maps of extreme precipitation for Spain, marking a significant step toward a national climate service for hydrometeorological extremes. Using long-term daily precipitation records from a dense network of stations and incorporating topographic data, the methodology combines the Generalized Pareto distribution with universal kriging to spatially interpolate distribution parameters. These maps offer reliable estimates of extreme precipitation quantiles, validated against station-level observations, and are based on a stationary modelling framework—an approach supported by recent findings showing the temporal stability of such extremes in Spain and considered more robust than non-stationary alternatives. Distinct spatial patterns emerge, with intense daily precipitation distributed mainly along the Mediterranean coast and high total event precipitation in the northwest and southwest, reflecting the influence of varied weather systems. To support decision-making, the study aggregates these high-resolution data at the provincial level, aligning risk information with administrative boundaries, and enhancing its relevance for policy and planning. Furthermore, the maps are made accessible via an interactive online platform ( https://retornolluvias.csic.es ), enabling users to explore localized hazard probabilities, thereby supporting adaptation in water management and civil protection, among others.

Chronic effects of wildfire smoke and criteria air pollutants on cardiovascular hospitalization rates in the contiguous US - Cheng Jin; Mahdieh Danesh Yazdi; Hanbing He; Edgar Castro; Joel D. Schwartz; Robert O. Wright; Yaguang Wei (Environmental Research, 2025)

How does the enhancement of carbon sequestration by non-native forests affect other ecosystem services? - Pilar Castro-Díez; Adrián Lázaro-Lobo; Romina D. Fernandez; Álvaro Alonso; Paula Cruces; Verónica Cruz-Alonso; Gary N. Ervin; Antonio Gallardo; Elena Granda; Daniel Gómez-Gras; Hélia Marchante; Daniel Moreno-Fernández; et al. (New Forests, 2025)

Gibberellin Regulates Sugar Metabolism and Modifies Cell Wall Composition in Soybean (Glycine max L. Merrill) - Raysa M. J. Sousa; Juliane M. Henschel; Diego S. Batista; Tatiane D. Silva; Sérgio H. S. Felipe; Gabriela Torres-Silva; Paulo V. L. Souza; Silvio A. Cândido-Sobrinho; Kristhiano Chagas; Kamila M. Castro; Evandro A. Fortini; Ludmila N. F. Correia; et al. (Journal of Plant Growth Regulation, 2025)

Microbiota dynamics across different developmental stages of the pepper weevil (Anthonomus eugenii Cano) - Carmen Y. Pelayo-Ayón; Jean P. González-Gómez; Roberto Gastelum-Luque; Nohelia Castro-del Campo; Juan D. Lira-Morales; Cristobal Chaidez (Biologia, 2025)

Oleic acid supplementation increases the PGE2:PGF2α ratio and alters expression of prostaglandin biosynthesis and maternal pregnancy recognition genes in bovine trophoblast cells in vitro - Valeska de Castro Lourenço; Letícia de Oliveira; Mariângela Bueno Cordeiro Maldonado; Laura Chuba Machado Rolniche; Lucas de Oliveira Bezerra; Isabella Rio Feltrin; Karine Galhego Morelli; Adriano Felipe Mendes; Cecilia Constantino Rocha; Caliê Castilho; Alessandra Bridi; Guilherme Pugliesi; et al. (Theriogenology, 2025)

Uncamarins A–D, oxindole alkaloids from Philippine Uncaria longiflora and their anti-amyloidogenic properties - Sarleen G. Castro; Eisuke Hosoya; Mariko Kitajima; Hiroyuki Nakamura; Joe Anthony H. Manzano; Grecebio Jonathan D. Alejandro; Mario A. Tan; Hayato Ishikawa (Phytochemistry, 2025)

Influence of local factors on the expression of the early Aptian OAE 1a – insights from a pelagic basin in the Western Tethys - José Manuel Castro; Cristina Sequero; Maria Luisa Quijano; Ginés A. de Gea; B. David A. Naafs; Richard D. Pancost (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

P06-20 Citidin Deaminase as a Predictive Biomarker of Antineoplastic Toxicity: Genotyping and Phenotyping - P. Castro-Sanchez; A. Corno Caparros; L. Pitaluga Poveda; A. Cardona Llorens; M.J. Prieto Castello; D. Marhuenda Amorós (Toxicology Letters, 2025)

P06-16 Impact of citidin deaminase genetic variants on capecitabine toxicity - P. Castro-Sanchez; A. Corno-Caparrós; L. Pitaluga-Poveda; A. Cardona-Llorens; D. Marhuenda-Amorós; M.J. Prieto-Castelló (Toxicology Letters, 2025)

Immunomodulatory properties of an arabinan polysaccharide extracted from Sida cordifolia: isolation, characterization and in vitro mechanism of action - Fang Cheng; Xiaobei Pan; Anna Notaro; Andrea Iovine; Antonio Molinaro; Cristina De Castro; Brian D. Green (Carbohydrate Polymers, 2025)

A synopsis of Senna ser. Bacillares (Leguminosae, Caesalpinioideae, Cassieae) in Brazil, including a remarkable new species from Amazonia - Alexandre Gibau De Lima; Vidal De Freitas Mansano; Marcelo Trovó Lopes De Oliveira; Gwilym Peter Lewis; Christine D. Bacon; Vinicius Castro Souza (Brittonia, 2025)
Senna (Leguminosae, Cassieae) comprises ca. 300 species mainly distributed throughout the Americas. Although the genus is speciose and taxonomically problematic, very few studies have addressed the systematics of Senna in recent years, and many taxonomic and nomenclatural issues remain unresolved. Senna sect. Chamaefistula ser. Bacillares is the most speciose of the American series of Senna and is the most problematic series in the genus. Based on fieldwork and extensive analysis of herbarium collections, we document the occurrence of 29 species of Senna ser. Bacillares in Brazil. This total includes Senna rionegrensis , which is newly described from Amazonia and distinguished by its short abaxial stamens. We provide a synopical treatment of the taxa of Senna ser. Bacillares occurring in Brazil, including identification keys, short morphological descriptions, taxonomic notes, and distributional and phenological data. This work contributes to the taxonomic knowledge of Senna ser. Bacillares in Brazil and serves as a baseline for our ongoing taxonomic revision.

The design of the Brazilian Sub-Daily Rainfall dataset (BR-SDR): two decades of high-time-resolution data in Brazil - Cristiano Das Neves Almeida; Guillaume Francis Bertrand; Filipe Carvalho Lemos; Emerson da Silva Freitas; Abner Lins Silva; José Lindemberg Vidal Barbosa; Marcela Antunes Meira; Geraldo Moura Ramos Filho; Gilson Barbosa Athayde Junior; Flávio José D’Castro Filho; Saulo Aires de Souza; Andrew Thomas Fullhart; et al. (Hydrological Sciences Journal, 2025)

Multiple anthelmintic drug resistance in the canine hookworm Ancylostoma caninum: AAVP position paper and research needs - Timothy G. Geary; Jason Drake; John S. Gilleard; Jeba R.J.Jesudoss Chelladurai; Pablo D. Jimenez Castro; Ray M. Kaplan; Antoinette E. Marsh; Craig R. Reinemeyer; Guilherme G. Verocai (Veterinary Parasitology, 2025)

First report of biological contaminants in household water in the Philippines and long-term viability of Acanthamoeba species in one-year-old household water sediment - Frederick R. Masangkay; Rafaella Maxine N. Almeda; Alianna Louise M. Abustan; Sarah Veronica F. Almendrala; Jan Camille B. Bathan; Jowey Shekainah C. Belandres; Maria Allana Angela M. Buenaventura; Lea May F. Cabansag; Gemina Bienne V. Caralian; Mikhaella Denise V. Cueva; Leizette P. Cata-Al; Rance Leander H. Clemente; et al. (Science of The Total Environment, 2025)

Contributions of Net-Map to sustainability action research - Sofía Valeria Cortés-Calderón; María D. López-Rodríguez; Amanda Jiménez-Aceituno; Antonio J. Castro; María Mancilla-García (Current Opinion in Environmental Sustainability, 2025)

A colorful new reporter system to evaluate gene expression in the archaeon Haloferax volcanii - Sofía D. Frecha; María I. Giménez; Roberto A. Paggi; Rosana E. De Castro; Micaela Cerletti (Extremophiles, 2025)

Fishing activities within Spanish marine protected areas in the Mediterranean Sea - María D. Castro-Cadenas; Martín Barreiros; Maria Bas; Miquel Ortega; Joachim Claudet; Marta Coll; Valerio Sbragaglia (Marine Policy, 2025)

Association of Aeromonas spp. with mortality and Perivisceral adipose tissue necrosis in redtail catfish (Phractocephalus hemioliopterus) - L. Caballero-Hernández; A. Castro-Alonso; M.J. Caballero; Á. Curros-Moreno; G. Montero-Hernández; D. Padilla; L. Marrero-Ponce; E. Montesdeoca-Morales (Journal of Comparative Pathology, 2025)

HIstopathological study of diseased sea urchins found dead in a rocky beach of Gran Canaria (Canary Islands) - M.J. Caballero; R. Nuñez-González; E. Montesdeoca-Morales; D. Padilla; J. Luis Martín Barrasa; G. Montero-Hernández; J. Juan Castro; A. Castro-Alonso (Journal of Comparative Pathology, 2025)

Retrospective characterization of viral induced skin and genital proliferative lesions in stranded cetaceans off the coasts of Spain - M.A. Jimenez Martinez; L. Sanchez Gil; I. Vargas Castro; J. Luis Crespo; M. Fayos Martinez; D. Garcia Parraga; J. Manuel Sanchez Vizcaino (Journal of Comparative Pathology, 2025)

Fatal necrotic-haemorrhagic pancreatitis associated with vibrio harveyi infection in a spiny butterfly ray (Gymnura altavela) - G. Montero-Hernández; A. Castro-Alonso; M.J. Caballero; Á. Curros-Moreno; D. Padilla; L. Caballero-Hernández; E. Montesdeoca-Morales; A. Fernández (Journal of Comparative Pathology, 2025)

The multifaceted spectra of power − A participatory network analysis on power structures in diverse dryland regions - Veronica Olofsson; Maria Mancilla Garcia; Antonio J. Castro; Sofía Cortés Calderón; Amadou Hamath Diallo; Amanda Jiménez Aceituno; María D. López-Rodríguez; Taís Sonetti Gonzalez; Amanda Sousa Silvino; Ana Paula Aguiar (Global Environmental Change, 2025)

First evidence of lead-induced impairment of intestinal digestive enzyme activity in birds - Ana C. Castro-Guijarro; Rodolfo J. Arias; Noelia C. Fernández; Juan G. Chediack; Fabricio D. Cid (Environmental Science and Pollution Research, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Body development, ingestive behaviour, and physiological responses of Nelore and Crossbred heifers - C. S. Santos; A. R. D. L. Souza; A. L. J. Ferraz; F. A. M. Sterza; R. V. Rohod; M. F. Castro; L. S. Amorim; M. C. E. Queiroz; G. B. Almeida; M. V. M. Oliveira; A. R. D. Santos; D. M. Oliveira (Tropical Animal Health and Production, 2025)

Utilization of different protein sources and intestinal histology in yellowtail snapper, Ocyurus chrysurus - Stephanie F. Velasquez; Leonardo Ibarra-Castro; John D. Stieglitz; Khanh Nguyen; Timothy J. Bruce; D. Allen Davis (Animal Feed Science and Technology, 2025)

Bird–window collisions: A comprehensive dataset for the Neotropical region - Augusto João Piratelli; Bianca Costa Ribeiro; Wesley Dáttilo; Luis‐Bernardo Vázquez; Anelisa Ferreira de Almeida Magalhães; Edna Maria Gomes Cavalcante; Eric Silva; Giovanna Viana Cruz; Gisele Regina Ruy; Juliana Laurito Summa; Júlia Milan; Leila Pedrosa; et al. (Ecology, 2025)
Our primary objective was to compile a comprehensive dataset on bird–window collisions throughout the Neotropical region, including both published and unpublished sources. On May 12, 2020, we extensively disseminated invitations to provide data via email and social media platforms. By providing a template worksheet, we required standardized information from collaborators to complete and register their data. To better understand how these data were acquired (e.g., incidental observations and systematic procedures), we sent out a survey to all collaborators. We established rigorous validation criteria for data inclusion and conducted thorough curation procedures to ensure accuracy. After the filtering process, we compiled a total of 4103 bird–window collision reports. These came from 11 Neotropical countries, dating from 1946 to 2020, and revealing distinct regional patterns and potential seasonal patterns. The five most frequent orders were Passeriformes (2451), Columbiformes (520), Apodiformes (377), Psittaciformes (202), and Piciformes (186). Data on bird–window collisions were collected through a local specific systematic protocol (1419), by chance (1252), by government agencies (742), and by other approaches (632), while a few reports were collected by unknown procedures (58). The volume of records across months in our dataset suggests that there may be temporal patterns, with peaks: the first one in March–April and the second one in October–November, which seem to align with the major migration and reproduction seasons. This dataset represents the first comprehensive effort in the Neotropical region focused on bird–window collision data, providing valuable insights for further scientific advancements and conservation policies. The data are free from copyright or proprietary restrictions. Please cite this data paper when using the data in publications or scientific presentations.

The use of egg quality parameters to evaluate the effect of a diet supplemented with algae and antioxidants in turbot (Scophthalmus maximus) - S. Ramos-Júdez; E. Fatsini; C. Marrero-Alemán; C. García-Pichel; P. Parente; D. Medina; C. Castro; E. Cabrita; C. C.V. Oliveira (Aquaculture, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Effects of dietary supplementation with slow-release urea coated with carnauba wax on intake, ingestive behavior, selectivity, ruminal parameters, performance and carcass traits of lambs - Tainan da Silva Batista; Leilson R. Bezerra; Pedro H.S. Mazza; Analivia M. Barbosa; Beatriz S.C. de Castro; Melissa D. Ferrer; Ana Carolina Ferreira; Jasiel S. de Morais; Edson C. da Silva Filho; Ronaldo L. Oliveira (Small Ruminant Research, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Late Holocene climate and environmental change in the Teuchitlán basin, Jalisco, Mexico - Gabriel Vazquez-Castro; Berenice Solis-Castillo; Priyadarsi D. Roy (Quaternary International, 2025)

Bio-desulfurization of different vulcanized rubber blends: An ecofriendly approach for end-of-life tires waste pollution - R. Andler; C. Cancino; F. González-Arancibia; J. Rojas; R. Castro; D. Kasai; V. Sanhueza (Journal of Environmental Chemical Engineering, 2025)

Can macro- or meso-scale coping capacity variables improve the classification of building flood losses? - D. Rodríguez Castro; M. Cools; S. Roucour; P. Archambeau; D. Molinari; A. R. Scorzini; C. Dessers; S. Erpicum; M. Pirotton; J. Teller; B. Dewals (Natural Hazards, 2025)

Regulatory role of annexin A1 in NLRP3 inflammasome activation in atopic dermatitis: insights from keratinocytes in human and murine studies - Rebeca D. Correia-Silva; Mab P. Corrêa; Maria Eduarda de Castro; Joaquim S. Almeida; Solange C. G. P. D’Ávila; Sonia M. Oliani; Karin V. Greco; Cristiane D. Gil (Journal of Molecular Medicine, 2025)

Mold in, mold out: Harvest bins harbor viable inoculum that can be reduced using novel sanitation methods to manage blue mold decay of apples - Dianiris Luciano-Rosario; Johanny Castro; Kari A. Peter; Kerik D. Cox; Jorge M. Fonseca; Verneta L. Gaskins; Wayne M. Jurick (Postharvest Biology and Technology, 2025)

The impact of Polylepis tarapacana on soil microbial communities in the Andean Dry Puna of Chile - Ignacio Gutiérrez-Cortés; Sofia Simpson; Marlene Manzano; Huber Villca; Benjamín Castro; Jean-Baptiste Ramond; María del Pilar Fernández Murillo; Fernando D. Alfaro (Journal of Arid Environments, 2025)

Trade-offs for healthy and sustainable diets in Europe: Social-ecological dynamics in an intensive agricultural system - A. Jiménez-Aceituno; M.D. López-Rodríguez; A.J. Castro; S. Cortés-Calderón; D. Collste; G. Aparicio; L. Rölfer; M.A. Bote; L. Marín; M.A. Gómez-Tenorio; B. González-Martín (Global Food Security, 2025)

Tree Diversity Increases Forest Temperature Buffering via Enhancing Canopy Density and Structural Diversity - Florian Schnabel; Rémy Beugnon; Bo Yang; Ronny Richter; Nico Eisenhauer; Yuanyuan Huang; Xiaojuan Liu; Christian Wirth; Simone Cesarz; Andreas Fichtner; Maria D. Perles‐Garcia; Georg J. A. Hähn; et al. (Ecology Letters, 2025)
Global warming is increasing the frequency and intensity of climate extremes. Forests may buffer climate extremes by creating their own attenuated microclimate below their canopy, which maintains forest functioning and biodiversity. However, the effect of tree diversity on temperature buffering in forests is largely unexplored. Here, we show that tree species richness increases forest temperature buffering across temporal scales over six years in a large‐scale tree diversity experiment covering a species richness gradient of 1 to 24 tree species. We found that species richness strengthened the cooling of hot and the insulation against cold daily and monthly air temperatures and temperature extremes. This buffering effect of tree species richness was mediated by enhanced canopy density and structural diversity in species‐rich stands. Safeguarding and planting diverse forests may thus mitigate negative effects of global warming and climate extremes on below‐canopy ecosystem functions and communities.

Deployment of portable, modular gas samplers as part of an atmospheric tracer experiment - Khiloni A. Shah; Nathan D. Anderson; Paul M. Baltoi; JohnPeter Bekker; Sarah T. Castro; Grayson N. Constantine; George J. Coutoumanos; Ethan P. Fowler; Kevin A. Guerra; Clayton C. Hudson; Nicholas M. Kaitschuck; John B. Lyle; et al. (Journal of Environmental Radioactivity, 2025)

Morphological and commercial quality variation of the stalked barnacle Pollicipes pollicipes: Patterns and drivers - A. Sousa; D. Jacinto; N. Penteado; D. Pereira; T. Silva; J.J. Castro; T. Cruz (Regional Studies in Marine Science, 2025)

Environmental factors determining the distribution of Limnoperna fortunei and its impact on benthic communities in the reservoirs of the Rio Negro (Uruguay)) - L. Capurro; J. Pereira; M. Castro; C. Ferrer; D. Fabián; P. Muniz; E. Brugnoli (Biological Invasions, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Hg, Cd, As, and Pb in surface sediments from the tropical coastal lagoon Estero Salado, Gulf of Guayaquil-Ecuador - Franklin I. Ormaza-González; Rubén D. Castro-Rendón; Ana Maridueña-Bravo; Nayiva Bobadilla-Cordova; Ivanna Ramos-Castañeda; Peter J. Statham (Frontiers in Marine Science, 2024)
The Gulf of Guayaquil (GG) is the most important tropical estuarine system of the eastern coast of South America, receiving an average water flow of about 1 650 m 3 s -1 from a river basin of approximately 33 700 km 2 . The city of Guayaquil surrounds the inner coastal lagoon of the Estero Salado (ES) that empties into the GG. This coastal lagoon is of high social, food production, and environmental importance for the city and the GG. However, there is limited high quality data on metal pollution in this zone, no recent information on Hg, and the extent to which sediment metal pollution extends into the GG is presently unknown. As, Cd, Pb, and Hg were analysed in surface sediments from the urban zone and gave average concentrations of 32.3, 2.08, 41.9, and 0.12 mg kg -1 (dry weight), respectively. Additionally, data were obtained for the first time for the El Morro Channel, south of the ES in the GG, which is expected to be a relatively pristine zone; average As, Cd, Pb and Hg concentrations were 6.6, 0.22, 7.9 and 0.02 mg kg -1 (dry weight), well below concentrations seen in the urban ES zone. Estimates of the geo-accumulation index for metal pollution, using the El Morro data as background values, were 1.7 (As), 2.7 (Cd), 1.8 (Pb) and 2.0 (Hg), making the ES class II and a moderately polluted estuary for As, Hg and Pb, but class III and “moderately to heavily polluted” for Cd. If the lowest concentrations of the EM samples are taken the ES is class III for As, IV for Hg and Pb, and V for Cd; id est, the ES would classify as a heavily to extremely polluted estuary regarding these metals. These data show the metal concentrations increase significantly as the main conurbation of Guayaquil is approached from offshore, indicating a strong anthropogenic source of metals from the city, with anticipated negative environmental impacts.

Monitoring macroplastics in aquatic and terrestrial ecosystems: Expert survey reveals visual and drone-based census as most effective techniques - L. Gallitelli; P. Girard; U. Andriolo; M. Liro; G. Suaria; C. Martin; A.L. Lusher; K. Hancke; MCM Blettler; O. Garcia-Garin; I.E. Napper; L. Corbari; et al. (Science of The Total Environment, 2024)

Applying the Three Horizons approach in local and regional scenarios to support policy coherence in SDG implementation: Insights from arid Spain - María D. López-Rodríguez; Amanda Jiménez-Aceituno; Cristina Quintas-Soriano; Juan Miguel Requena-Mullor; Enrica Garau; Daniela Alba-Patiño; Irene Otamendi-Urroz; Ana Paula D. Aguiar; Sofía Cortés-Calderón; Antonio J. Castro (Global Environmental Change, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Pinus cembroides, and P. orizabensis grafts, a viable option for pink pine nut production - Sandra L. Castro-Garibay; Omegar Cruz-Arvizu; Isaí Monroy-González; Alma D. Abarca-Cervantes; Iris J. Cruz-Larios; Marcelina Arguello-Hernández (New Forests, 2024)

Emotional attachment and philosophical worldviews explain human connectedness to nature in abandoned rural Spain - C. López-Zayas; A. J. Castro; J. M. Requena-Mullor; M. D. López-Rodríguez; E. Garau; C. Quintas-Soriano (Sustainability Science, 2024)
Land abandonment and rural depopulation are escalating worldwide, presenting sustainability dilemmas for both rural and urban regions. However, there remains a dearth of research on the sociocultural dimensions of abandonment from a local standpoint. This investigation focuses on a case study conducted in southeastern Spain, wherein a social survey was used to evaluate the perspectives of local communities concerning human–nature interconnectedness, land abandonment, and their impacts on quality of life. A survey campaign was administered in the case study region during the spring of 2021, and 122 surveys were collected. The findings identify, in the context of the progressive abandonment of rural lands in Spain, key factors that explain the desire of local people to inhabit and not abandon rural regions in southeastern Spain. Our results also show a strong connection between people and nature in rural Spain, which is explained by the capacity of locals to form relational values in rural environments and the existence of philosophical worldviews and emotional attachments to rural lifestyles. However, barriers to not abandoning rural environments were also identified, including a lack of professional and economic opportunities. Our results suggest that the mitigation of depopulation in rural areas in Spain requires actions to foster land stewardship and address socioeconomic imbalances.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

P13-07 Uranium and kidney cancer: insights from genetically engineered mouse models in the UKCAN project - L. De Castro; O. Claude; M. Brisset; C. Gillot; A. Manoury; A. Sache; F. Voyer; D. Suhard; V. Monceau; C. Bouvier-Capely; C. Ibanez; Y. Guéguen (Toxicology Letters, 2024)

Towards scaling up of the electrochemical production of Caro’s acid: Electrode size and/or stacking? - M. Pilar Castro; Miguel A. Montiel; Ismael F. Mena; J. Gäbler; D. Barton; Cristina Sáez; Manuel A. Rodrigo (Chemical Engineering Journal, 2024)

Antimicrobial resistance patterns of Staphylococcus spp. isolated from clinical specimens of companion animals in Northern Portugal, 2021–2023 - D. Araújo; R. Oliveira; B.L. Silva; J. Castro; C. Ramos; F. Matos; C. Almeida; S. Silva (The Veterinary Journal, 2024)

Novel designs of blade mixer impellers from the discrete element method and topology optimization - Michael T. Castro; Joey D. Ocon (Chemical Engineering Journal, 2024)

Investigating impacts of the mycothiazole chemotype as a chemical probe for the study of mitochondrial function and aging - Naibedya Dutta; Joe A. Gerke; Sofia F. Odron; Joseph D. Morris; Adam Hruby; Juri Kim; Toni Castro Torres; Sarah J. Shemtov; Jacqueline G. Clarke; Michelle C. Chang; Hooriya Shaghasi; Marissa N. Ray; et al. (GeroScience, 2024)
Small molecule inhibitors of the mitochondrial electron transport chain (ETC) hold significant promise to provide valuable insights to the field of mitochondrial research and aging biology. In this study, we investigated two molecules: mycothiazole (MTZ) - from the marine sponge C. mycofijiensis and its more stable semisynthetic analog 8- O -acetylmycothiazole (8-OAc) as potent and selective chemical probes based on their high efficiency to inhibit ETC complex I function. Similar to rotenone (Rote), MTZ, a newly employed ETC complex I inhibitor, exhibited higher cytotoxicity against cancer cell lines compared to certain non-cancer cell lines. Interestingly, 8-OAc demonstrated greater selectivity for cancer cells when compared to both MTZ and Rote, which has promising potential for anticancer therapeutic development. Furthermore, in vivo experiments with these small molecules utilizing a C. elegans model demonstrate their unexplored potential to investigate aging studies. We observed that both molecules have the ability to induce a mitochondria-specific unfolded protein response (UPR MT ) pathway, that extends lifespan of worms when applied in their adult stage. We also found that these two molecules employ different pathways to extend lifespan in worms. Whereas MTZ utilizes the transcription factors ATFS-1 and HSF1, which are involved in the UPR MT and heat shock response (HSR) pathways respectively, 8-OAc only required HSF1 and not ATFS-1 to mediate its effects. This observation underscores the value of applying stable, potent, and selective next generation chemical probes to elucidate an important insight into the functional roles of various protein subunits of ETC complexes and their regulatory mechanisms associated with aging. Graphical Abstract

Trophic ecology of sympatric sea turtles in the tropical Atlantic coast of Brazil - Moises F. Bezerra; Cesar A. Barrios-Rodriguez; Carlos E. Rezende; Melania C. López-Castro; Luiz D. Lacerda (Marine Environmental Research, 2024)

A methodological approach for integrating human emotions in protected areas management: Insights from SE Spain - Enrica Garau; Juan M. Requena-Mullor; Cristina Quintas-Soriano; María D. López-Rodríguez; Irene Otamendi-Urroz; Mariano Oyarzabal; Antonio J. Castro (Landscape and Urban Planning, 2024)

The key role played by mesoporous alumina as binder for obtaining ultra-hard CaO based pellets for thermochemical heat storage leveraging the CaO/CaCO3 cycle - D. Castro-Yáñez; M. Erans; A. Peral; R. Sanz; J. González-Aguilar; M. Romero; L. Briones; E.S. Sanz-Pérez; J.M. Escola (Journal of Cleaner Production, 2024)

Long-term exposure to PM2.5 species and all-cause mortality among Medicare patients using mixtures analyses - Mahdieh Danesh Yazdi; Heresh Amini; Yaguang Wei; Edgar Castro; Liuhua Shi; Joel D. Schwartz (Environmental Research, 2024)

Resilience of Ricinus communis L. to high temperatures during germination and seedling growth resulting from efficient superoxide dismutase modulation - Valdir G. Neto; Wilco Ligterink; Henk W. M. Hilhorst; Isabela D. Santos; Carine R. Teixeira; Emily E. Santos; Marta B. Loureiro; Daniele Takahashi; Luzimar G. Fernandez; Paulo R. Ribeiro; Renato D. De Castro (Brazilian Journal of Botany, 2024)

What makes a cyanobacterial bloom disappear? A review of the abiotic and biotic cyanobacterial bloom loss factors - Ted D. Harris; Kaitlin L. Reinl; Marzi Azarderakhsh; Stella A. Berger; Manuel Castro Berman; Mina Bizic; Ruchi Bhattacharya; Sarah H. Burnet; Jacob A. Cianci-Gaskill; Lisette N. de Senerpont Domis; Inge Elfferich; K. Ali Ger; et al. (Harmful Algae, 2024)

Reinforcement of alkali-activated cements based matrices using olive pruning fibres as an alternative to traditional fibres - M.A. Gómez-Casero; L. Pérez-Villarejo; E. Castro; D. Eliche-Quesada (Sustainable Chemistry and Pharmacy, 2024)

A spatial framework for improved sanitation to support coral reef conservation - Caitlin D. Kuempel; Jacqueline Thomas; Amelia S. Wenger; Stacy D. Jupiter; Andrés F. Suárez-Castro; Nabeela Nasim; Carissa J. Klein; Ove Hoegh-Guldberg (Environmental Pollution, 2024)

Terminalia catappa L. leaf extract interferes with biofilm formation of Vibrio parahaemolyticus and enhances immune response of Penaeus vannamei against acute hepatopancreatic necrosis disease (AHPND) - Sheila D.A. Mantaring; Jan Rotsen Kyle Delos Santos; Romulo Estrella; John Paulo G. Jose; Ian John L. Castro; Ursela G. Bigol; John Paul Matthew D. Guzman (Aquaculture, 2024)

Embryo-maternal communication mediated by extracellular vesicles in the early stages of embryonic development is modified by in vitro conditions - C. Aguilera; Y.S. Wong; M.A. Gutierrez-Reinoso; A.E. Velásquez; B. Melo-Báez; J. Cabezas; D. Caamaño; F. Navarrete; F.O. Castro; L.l. Rodriguez-Alvarez (Theriogenology, 2024)

Buoys are non-indigenous fouling hotspots in marinas regardless of their environmental status and pressure - Juan Sempere-Valverde; María D. Castro-Cadenas; José Manuel Guerra-García; Free Espinosa; José Carlos García-Gómez; Macarena Ros (Science of The Total Environment, 2024)

Bread fermentation monitoring through NIR spectroscopy and PLS-DA. Determining the optimal fermentation point in bread doughs - D. Castro-Reigía; I. García; S. Sanllorente; L.A. Sarabia; J.M. Amigo; M.C. Ortiz (Journal of Food Engineering, 2024)

Improvement in Sunlight-Irradiated Photocatalytic Activity and Stability of Ca10(PO4)6(OH)2/g-C3N4 for Dye Mixture Degradation - Mário A. M. Castro; José Victor S. Galvão; Débora F. S. Morais; Marcio D. Teodoro; Ricardo P. Souza; Maurício R. D. Bomio; Fabiana V. Motta (Water, Air, & Soil Pollution, 2024)

How complex is the hidden species diversity of the teleost Plotosus genus? - Elsa Froufe; André Gomes-dos-Santos; Ana Matos; Jonathan Wilson; Salman Malakpourkolbadinezhad; Daniel D. Pereira; Randal Singer; L. Filipe C. Castro (Ichthyological Research, 2024)
The striped eel catfish, Plotosus lineatus was first described by Thunberg in 1787 from the Indo-Pacific region in the East Indian Ocean. Since then, the species has been recorded in various marine and brackish habitats in Japan, southern Korea, the Ogasawara Islands, Australia, Lord Howe Island, Palau and Yap in Micronesia, East Africa to Samoa, Madagascar, Red Sea and the Persian Gulf. Occurrences of this species have also been registered in the Mediterranean Sea, a non-native location, indicating a possible biological invasion event. Despite its long history, the taxonomic status of the P. lineatus species complex remains puzzling and uncertain. Here, we analysed all the available mitochondrial cytochrome c oxidase subunit 1 sequences (NCBI and BOLD) from specimens covering the current known distribution range, in an attempt to clarify the evolutionary relationships of different lineages within this species. We deduce nine monophyletic Lineages - I–IX , of P. lineatus with Kimura-2P distances ranging from 2% to 16%, with a mean intraspecific distance of 6%. Strikingly, Lineage V is composed uniquely of Mediterranean-captured individuals, with an unknown evolutionary origin. These findings strongly suggest the need for a careful species taxonomic reassessment. Some Lineages are composed of individuals from specific geographic locations (e.g., Australia and Indonesia), while others include specimens from broader geographic areas (e.g., almost all Indo-Pacific coastline). Additionally, several deposited sequences are most likely the result of morphology-based misidentifications. Due to the biological invasive potential, as well as the use of the species as a valuable physiology model, the P. lineatus species complex requires further attention. Overall our study offers a clear framework for future comparative studies of striped eel catfish individuals captured from different ecosystems.

Adaptation of sea turtles to climate warming: Will phenological responses be sufficient to counteract changes in reproductive output? - M. M. P. B. Fuentes; A. J. B. Santos; A. Abreu‐Grobois; R. Briseño‐Dueñas; J. Al‐Khayat; S. Hamza; S. Saliba; D. Anderson; K. W. Rusenko; N. J. Mitchell; M. Gammon; B. P. Bentley; et al. (Global Change Biology, 2024)
Sea turtles are vulnerable to climate change since their reproductive output is influenced by incubating temperatures, with warmer temperatures causing lower hatching success and increased feminization of embryos. Their ability to cope with projected increases in ambient temperatures will depend on their capacity to adapt to shifts in climatic regimes. Here, we assessed the extent to which phenological shifts could mitigate impacts from increases in ambient temperatures (from 1.5 to 3°C in air temperatures and from 1.4 to 2.3°C in sea surface temperatures by 2100 at our sites) on four species of sea turtles, under a “middle of the road” scenario (SSP2‐4.5). Sand temperatures at sea turtle nesting sites are projected to increase from 0.58 to 4.17°C by 2100 and expected shifts in nesting of 26–43 days earlier will not be sufficient to maintain current incubation temperatures at 7 (29%) of our sites, hatching success rates at 10 (42%) of our sites, with current trends in hatchling sex ratio being able to be maintained at half of the sites. We also calculated the phenological shifts that would be required (both backward for an earlier shift in nesting and forward for a later shift) to keep up with present‐day incubation temperatures, hatching success rates, and sex ratios. The required shifts backward in nesting for incubation temperatures ranged from −20 to −191 days, whereas the required shifts forward ranged from +54 to +180 days. However, for half of the sites, no matter the shift the median incubation temperature will always be warmer than the 75th percentile of current ranges. Given that phenological shifts will not be able to ameliorate predicted changes in temperature, hatching success and sex ratio at most sites, turtles may need to use other adaptive responses and/or there is the need to enhance sea turtle resilience to climate warming.

Heterogeneous photosensitization for water reuse in cellars: evaluation of silica, spongin, and chitosan as carrier material - Andreia D. Santos; Eduardo Pinho; Patrícia Reis; Rui C. Martins; Marta Gmurek; Anabela Nogueira; Sérgio Castro-Silva; Luís M. Castro; Rosa M. Quinta-Ferreira (Environmental Science and Pollution Research, 2023)
Photosensitization, a powerful oxidation reaction, offers significant potential for wastewater treatment in the context of industrial process water reuse. This environmentally friendly process can be crucial in reducing water consumption and industrial pollution. The ultimate goal is to complete process water reuse, creating a closed-loop system that preserves the inherent value of water resources. The photosensitized oxidation reaction hinges on three essential components: the photosensitizer, visible light, and oxygen. In this study, we assess the performance of three distinct materials—silica, chitosan, and spongin—as carrier materials for incorporating the phthalocyanine photosensitizer (ZnPcS 4 ) in the heterogenous photosensitization process. Among the three materials under study, chitosan emerged as the standout performer in reactor hydrodynamic performance. In the photooxidation process, the photosensitizer ZnPcS 4 exhibited notable efficacy, resulting in a significant reduction of approximately 20 to 30% in the remaining COD concentration of the cellar wastewater. Chitosan demonstrated exceptional hydrodynamic characteristics and displayed a favorable response to pH adjustments within the range of 8 to 10, outperforming the other two carrier materials. To further enhance the efficiency of continuous operation, exploring methods for mitigating photosensitizer bleaching within the reaction medium and investigating the impact of different pH values on the process optimization would be prudent.

Modeling the interannual variability in Maipo and Rapel river plumes off central Chile - Julio Salcedo-Castro; Antonio Olita; Freddy Saavedra; Gonzalo S. Saldías; Raúl C. Cruz-Gómez; Cristian D. De la Torre Martínez (Ocean Science, 2023)
River plumes have a direct influence on coastal environments, impacting coastal planktonic and benthic communities, including fishery resources. In general, the main drivers of river plume dynamics are the river discharge and the alongshore wind stress, whereas the tides and topography play a secondary role. In central Chile, rivers flowing into the eastern Pacific have a relatively short path on land, with a high slope and a mixed snow–rain regime. This study aims to understand the interannual variability in the plumes of the Maipo and Rapel rivers in the coastal/shelf area off central Chile and their influence on local ocean dynamics. We used the Coastal and Regional Ocean Community (CROCO) model, with 1 km horizontal resolution and 20 sigma levels, to simulate the ocean dynamics for the period 2003–2011. The results show that the plume's area coverage and coastal ocean salinity are strongly correlated with the river discharges. The predominant northeastward winds control the plumes' orientation toward the northwest. However, episodes of southeastward winds in winter can reverse the plumes' direction, promoting their attachment to the coast and southward transport. Results also show a salification trend linked to the severe droughts hitting central Chile during the studied period. This salification determines a change in local dynamics which could be more frequent in future scenarios of climate change with a significant lack of rain and river discharges along central Chile.

Recruitment models after reduced impact logging in the Amazon rainforest - Erica Karolina Barros de Oliveira; Alba Valéria Rezende; Leonidas Soares Murta Júnior; Lucas Mazzei; Renato Vinícios Oliveira Castro; Marcus Vinicio Neves d'Oliveira; Gileno Brito de Azevedo (Forest Ecology and Management, 2023)

Trends in valuation approaches for cultural ecosystem services: A systematic literature review - Laura Andreina Matos Márquez; Eva Caroline Nunes Rezende; Karine Borges Machado; Emilly Layne Martins do Nascimento; Joana D'arc Bardella Castro; João Carlos Nabout (Ecosystem Services, 2023)

Monitoring corn nitrogen nutrition index from optical and synthetic aperture radar satellite data and soil available nitrogen - Adrián M. Lapaz Olveira; Mauricio Castro-Franco; Hernán R. Saínz Rozas; Walter D. Carciochi; Mónica Balzarini; Oscar Avila; Ignacio Ciampitti; Nahuel I. Reussi Calvo (Precision Agriculture, 2023)

Long‐term observed changes of air temperature, relative humidity and vapour pressure deficit in Bolivia, 1950–2019 - B. Fernández‐Duque; S. M. Vicente‐Serrano; O. Maillard; F. Domínguez‐Castro; D. Peña‐Angulo; I. Noguera; C. Azorin‐Molina; A. El Kenawy (International Journal of Climatology, 2023)
This study analyzes the long‐term observed changes of mean (Tmean), maximum (Tmax) and minimum (Tmin) air temperatures, relative humidity (RH) and vapour pressure deficit (VPD) at different elevation ranges across Bolivia from 1950 to 2019. The linear trends in air temperature series present a significant increase, with no substantial seasonal or spatial differences. On an annual basis, RH exhibited a non‐significant decrease (−0.08% decade −1 ), while VPD showed a significant increase (0.01 hPa decade −1 ) ( p

Identifying and prioritizing demersal fisheries restricted areas based on combined ecological and fisheries criteria: The western Mediterranean - Miquel Ortega; María D. Castro-Cadenas; Jeroen Steenbeek; Marta Coll (Marine Policy, 2023)

Fishers' communication as a critical factor for tuna catches and potential benefits of traceability draws small-scale Fishers to program - Edison D. Macusi; Miko Mariz C. Castro; Ivy M. Nallos; Christine P. Perales (Ocean & Coastal Management, 2023)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Results from the Radiation Assessment Detector on the International Space Station: Part 3, combined results from the CPD and FND - C. Zeitlin; A.J. Castro; K.B. Beard; B.M. Hayes; M. Abdelmelek; D. Laramore; A.S. Johnson; N. Stoffle; R.F. Wimmer-Schweingruber; S. Löffler; R.R. Rios (Life Sciences in Space Research, 2023)

Basking in the sun: how mosses photosynthesise and survive in Antarctica - Hao Yin; Alicia V. Perera-Castro; Krystal L. Randall; Johanna D. Turnbull; Melinda J. Waterman; Jodie Dunn; Sharon A. Robinson (Photosynthesis Research, 2023)
The Antarctic environment is extremely cold, windy and dry. Ozone depletion has resulted in increasing ultraviolet-B radiation, and increasing greenhouse gases and decreasing stratospheric ozone have altered Antarctica’s climate. How do mosses thrive photosynthetically in this harsh environment? Antarctic mosses take advantage of microclimates where the combination of protection from wind, sufficient melt water, nutrients from seabirds and optimal sunlight provides both photosynthetic energy and sufficient warmth for efficient metabolism. The amount of sunlight presents a challenge: more light creates warmer canopies which are optimal for photosynthetic enzymes but can contain excess light energy that could damage the photochemical apparatus. Antarctic mosses thus exhibit strong photoprotective potential in the form of xanthophyll cycle pigments. Conversion to zeaxanthin is high when conditions are most extreme, especially when water content is low. Antarctic mosses also produce UV screening compounds which are maintained in cell walls in some species and appear to protect from DNA damage under elevated UV-B radiation. These plants thus survive in one of the harshest places on Earth by taking advantage of the best real estate to optimise their metabolism. But survival is precarious and it remains to be seen if these strategies will still work as the Antarctic climate changes.

Whose values count? A review of the nature valuation studies with a focus on justice - M Schaafsma; S Ahn; AJ Castro; N Dendoncker; A Filyushkina; D González-Jiménez; Mariaelena Huambachano; N Mukherjee; TH Mwampamba; J Ngouhouo-Poufoun; I Palomo; R Pandit; et al. (Current Opinion in Environmental Sustainability, 2023)

Multi-analytical characterization of an oncoid from a high altitude hypersaline lake using techniques employed in the Mars2020 and Rosalind Franklin missions on Mars - J. Huidobro; J.M. Madariaga; D. Carrizo; J.L. Laserna; F. Rull; J. Martínez-Frías; J. Aramendia; L. Sánchez-García; L. García-Gómez; F.A. Vignale; M.E. Farías; M. Veneranda; et al. (Analytica Chimica Acta, 2023)

Temporal and spatial evolution of the 2021 eruption in the Tajogaite volcano (Cumbre Vieja rift zone, La Palma, Canary Islands) from geophysical and geodetic parameter analyses - M. B. Benito; G. E. Alvarado; M. Marchamalo; J. G. Rejas; P. Murphy; R. Franco; D. Castro; C. Garcia-Lanchares; J. Sanchez (Natural Hazards, 2023)
The eruption of the Tajogaite volcano in 2021, in the Cumbre Vieja rift zone (La Palma, Canary Islands), is the most recent but also the most damaging and longest-lasting eruption on the island since historical records began. We analyzed geophysical parameters (seismicity, surface deformation, thermal anomalies, and volcanic activity) with the aim of reconstructing the temporal development of the magma plumbing system. The seismic sequence (> 9000 events, mbLg ≤ 5.0) can be grouped into nine distinct phases, which correspond to well-separated spatial clusters and distinct earthquake regimes. A strong premonitory thermal anomaly was calculated on July 2021 in the South of La Palma. The source of the magma was within the upper mantle (40–20 km depth). A second magma budget (< 15 km depth) indicated a short-term stagnation of alkaline magma within the lower crust, near the Moho. The outline of these earthquakes delineates the magma pathway. Just before and immediately after the eruption (phases 2 and 3), the high-frequency seismicity in the mantle disappeared completely, reappearing ten days after the eruption started. The pattern of deformation began before the eruption with a breakpoint around September 11, after which, deformation accelerated sharply, followed by stabilization in phase 3 and a decrease in the following phases. The level of deformation suggested that a shallow magma intrusion was established. Based on the historical eruptive pattern, it is possible to infer two possible hazard-forecast scenarios: (a) the volcano could enter a prolonged phase of tranquility for more than one century or, (b) a new eruption could occur between ca. 2045 and 2065, with a slightly shorter duration than this recent one. Therefore, if the more pessimistic scenario is assumed, appropriate territorial planning is required.

Geometric morphometrics as a tool to identify Dasypodini osteoderms: Implications for the oldest records of Dasypus - Juan S. Salgado-Ahumada; Marcos D. Ercoli; Alicia Álvarez; Mariela C. Castro; Martín R. Ciancio (Journal of Mammalian Evolution, 2023)

Biochar and Forage Peanut improve pastures: Evidence from a field experiment in Brazil - Agnieszka E. Latawiec; Aline F. Rodrigues; Katarzyna A. Korys; Maiara Mendes; Marcio Rangel; Ana Castro; Wenceslau Teixeira; Judson F. Valentim; Ednaldo Araujo; Luiz Fernando Duarte de Moraes; Vinicius Pacheco; Marcos Mendes; et al. (Agriculture, Ecosystems & Environment, 2023)

Conjugated linoleic acid supplementation changes prostaglandin concentration ratio and alters the expression of genes involved in maternal-fetal recognition from bovine trophoblast cells in vitro - Mariângela Bueno Cordeiro Maldonado; Valeska de Castro Lourenço; Lucas de Oliveira Bezerra; Isabella Rio Feltrin; Adriano Felipe Mendes; Cecilia Constantino Rocha; Guilherme Pugliesi; Alan D. Ealy; Claudia Maria Bertan Membrive; Marcelo Fábio Gouveia Nogueira (Theriogenology, 2023)

Electrocoagulation treatment of furniture industry wastewater - Carolina Vicente; João R. Silva; Andreia D. Santos; João F. Silva; Jorge T. Mano; Luis M. Castro (Chemosphere, 2023)

Review of the adsorbents/catalysts for the removal of sulfur compounds from natural gas - Percival Soni Castro; Gerson Martinez Zuniga; William Holmes; Prashanth R. Buchireddy; Daniel D. Gang; Emmanuel Revellame; Mark Zappi; Rafael Hernandez (Gas Science and Engineering, 2023)

Water reclamation via membrane distillation applied to textile dye wastewater using a commercial poly(vinylidene fluoride) membrane - H. Ramlow; B. de Castro Santos; C. M. Tolentino Filho; C. D. K. Cavalcanti; R. A. F. Machado; C. Marangoni (International Journal of Environmental Science and Technology, 2023)

Rajids ovipositing on marine litter: A potential threat to their survival - Miguel Valderrama-Herrera; Sara Amada Cardenas; Carlos Calvo-Mac; Renzo Gustavo Celi-Vértiz; Valeria Liz Chumpitaz-Levano; Walter Eduardo Flores-Miranda; Zoila M.T. Lopez-Tirado; Mariana Molina-Alvarez; Diana N. Rubio-Cheon; Maryalejandra Trucios-Castro; Melisa D. Fernández Severini; Ana D. Forero López; et al. (Marine Pollution Bulletin, 2023)

Exploring the prevalence and antibiotic resistance profile of Klebsiella pneumoniae and Klebsiella oxytoca isolated from clinically ill companion animals from North of Portugal - D. Araújo; J. Castro; F. Matos; R. Oliveira; C. Ramos; C. Almeida; S. Silva (Research in Veterinary Science, 2023)

Modelling aboveground biomass and productivity and the impact of climate change in Mediterranean forests of South Spain - Aurelio D. Herraiz; Pablo César Salazar-Zarzosa; Francisco Javier Mesas; Salvador Arenas-Castro; Paloma Ruiz-Benito; Rafael Villar (Agricultural and Forest Meteorology, 2023)

Quantification of Wood Biomass in an Area of Sustainable Annual Production in the Brazilian Semiarid Region Aiming at Generating Renewable Energy - R. C. Santos; F. G. C. Pareyn; C. P. S. Santos; D. Minini; S. M. G. Rocha; F. J. O. Souza; L. F. C. Cezario; A. F. Dias Júnior; R. V. O. Castro (BioEnergy Research, 2023)

Sulfolipid substitution ratios of Microcystis aeruginosa and planktonic communities as an indicator of phosphorus limitation in Lake Erie - Robbie M. Martin; Maddie K. Denney; Helena L. Pound; Justin D. Chaffin; George S. Bullerjahn; R. Michael L. McKay; Arthur Zastepa; Katarina A. Jones; Hector F. Castro; Shawn R. Campagna; Steven W. Wilhelm (Limnology and Oceanography, 2023)
Phosphorus (P) availability frequently limits primary production in lakes, influences the physiology of phytoplankton, shapes community structure, and can stimulate or constrain the formation of cyanobacterial blooms. Given the importance of P, numerous methods are available to assess P stress in phytoplankton communities. Marine phytoplankton are known to substitute sulfolipids for phospholipids in response to P limitation. We asked whether sulfolipid substitution might serve as an additional indicator of P stress in freshwater phytoplankton communities. The question was addressed using cultures of Microcystis aeruginosa , Lake Erie microcosms, and surveys of lipid profiles in Lake Erie during a Microcystis spp. bloom. Peak area response ratios of the intact polar lipids sulfoquinovosyldiacylglycerol (SQDG) to phosphatidylglycerol (PG) were used as the metric of lipid substitution. In cultures of M. aeruginosa NIES‐843, the SQDG : PG ratio increased from ~ 0.9 to ~ 3.3 with decreasing P concentration. In P‐limited communities, the SQDG : PG ratio increased from ~ 6 to ~ 11 after 48 h in microcosm controls, while P amendments reduced the ratio to ~ 3. In Lake Erie surveys, the SQDG : PG ratio ranged from ~ 0.4 to ~ 7.4 and was negatively correlated (Pearson r = −0.62) with total dissolved P. The SQDG : PG ratio was not correlated with concentrations of chlorophyll a , soluble reactive P, or N : P molar ratios. These results demonstrated that M. aeruginosa and Microcystis ‐dominated communities remodel lipid profiles in response to P scarcity, providing a potential short‐term, time‐integrated biomarker of nutrient history and P stress in fresh waters.

Genetic population structure of Pseudoplatystoma corruscans (Siluriformes: Pimelodidae) and evidence of temporal variation in structure - Eva C. Rueda; Carolina B. Machado; Veronica Castro; Alline Braga‐Silva; Guillermo Ojeda; Facundo Vargas; Gisela Loretán; Patricia D. Freitas; Pedro M. Galetti; Guillermo Ortí (Journal of Fish Biology, 2023)
Surubim ( Pseudoplatystoma corruscans , Pimelodidae) are migratory catfish native to the rivers in the La Plata and São Francisco basins. They are piscivores that attain considerable body sizes and are a valuable economic resource. Surubim exhibits extensive migrations during its life cycle that may affect the population structure at vast geographic scales. The authors examined the genetic diversity and population genetic structure of P. corruscans using microsatellite markers from a comprehensive sampling of 260 individuals from the Upper and Lower Paraná River. They identified two well‐differentiated genetic clusters corresponding to a natural geographic barrier historically separating Upper and Lower Paraná regions. They also demonstrated temporal variation in population genetic structure at a site in Lower Paraná close to the confluence with the Paraguay River, most likely explained by the influx of migrant fishes at certain times of the year.

Over-expression of the barley Phytoglobin 1 (HvPgb1) evokes leaf-specific transcriptional responses during root waterlogging - Robert D. Hill; James de Castro; Mohammed M. Mira; Abir U. Igamberdiev; Kim H. Hebelstrup; Sylvie Renault; Wayne Xu; Ana Badea; Claudio Stasolla (Journal of Plant Physiology, 2023)

Assessment of vapor pressure deficit variability and trends in Spain and possible connections with soil moisture - I. Noguera; S.M. Vicente-Serrano; D. Peña-Angulo; F. Domínguez-Castro; C. Juez; M. Tomás-Burguera; J. Lorenzo-Lacruz; C. Azorin-Molina; A. Halifa-Marín; B. Fernández-Duque; A. El Kenawy (Atmospheric Research, 2023)

Experimental evidence in a poison frog model suggests that tadpole transport on the dorsum may affects warning signal effectiveness in poison frogs - María Paula Toro-Gómez; Juan D. Carvajal-Castro; Santiago Casas-Cardona; Fernando Vargas-Salinas (Evolutionary Ecology, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Evaluation of lead exposition length on the liver and intestinal histoarchitecture of eared dove (Zenaida auriculata) - Verónica P. Filippa; Emilce L. Tabares; Ana C. Castro-Guijarro; Juan G. Chediack; Fabricio D. Cid (Environmental Science and Pollution Research, 2023)

Losartan impairs HTR-8/SVneo trophoblast migration through inhibition of angiotensin II-induced pro-inflammatory profile in human endometrial stromal cells - Rosario Macchi; Agustina D. Sotelo; Andrea C. Parrado; Luciana S. Salaverry; Guillermo A. Blanco; Marisa S. Castro; Estela B. Rey-Roldán; Andrea M. Canellada (Toxicology and Applied Pharmacology, 2023)

A letter to the editor about the article “The modularity codes” - Omar Paredes; Elsa Magaña-Cuevas; Sorpresa Lora-Castro; Juan D. Serna-Grilló; D.Y. De la Mora; Diana Ríos Patiño; Rebeca Romo-Vázquez; J. Alejandro Morales (Journal of Theoretical Biology, 2023)

Karstified zone interpretation using deep learning algorithms: Convolutional neural networks applications and model interpretability with explainable AI - Marcos V.G. Jacinto; Adrião D. Doria Neto; David L. de Castro; Francisco H.R. Bezerra (Computers & Geosciences, 2023)

Coral disease outbreak at the remote Flower Garden Banks, Gulf of Mexico - Michelle A. Johnston; Michael S. Studivan; Ian C. Enochs; Adrienne M. S. Correa; Nicole Besemer; Ryan J. Eckert; Kimberly Edwards; Ryan Hannum; Xinping Hu; Marissa Nuttall; Kelly O’Connell; Ana M. Palacio-Castro; et al. (Frontiers in Marine Science, 2023)
East and West Flower Garden Bank (FGB) are part of Flower Garden Banks National Marine Sanctuary (FGBNMS) in the northwest Gulf of Mexico. This geographically-isolated reef system contains extensive coral communities with the highest coral cover (>50%) in the continental United States due, in part, to their remoteness and depth, and have historically exhibited low incidence of coral disease and bleaching despite ocean warming. Yet in late August 2022, disease-like lesions on seven coral species were reported during routine monitoring surveys on East and West FGB (2.1–2.6% prevalence). A series of rapid response cruises were conducted in September and October 2022 focused on 1) characterizing signs and epidemiological aspects of the disease across FGB and within long-term monitoring sites, 2) treating affected coral colonies with Base 2B plus amoxicillin, and 3) collecting baseline images through photostations and photomosaics. Marginal and/or multi-focal lesions and tissue loss were observed, often associated with substantial fish and invertebrate predation, affecting the dominant coral species Pseudodiploria strigosa (7–8% lesion prevalence), Colpophyllia natans (11–18%), and Orbicella spp. (1%). Characterizing this disease event during its early epidemic phase at East and West FGB provides a critical opportunity to observe how coral disease functions in a relatively healthy coral ecosystem versus on reefs chronically affected by various stressors (e.g., Caribbean reefs adjacent to urban centers). Insights into the etiology, spread, and impacts of the disease can ultimately inform efforts to mitigate its effects on coral communities.

Environmental application of a cost-effective smartphone-based method for COD analysis: Applicability in the electrochemical treatment of real wastewater - Cláudio M. de Castro; Paulo Olivi; Karla Caroline de Freitas Araújo; Inalmar D. Barbosa Segundo; Elisama V. dos Santos; Carlos A. Martínez-Huitle (Science of The Total Environment, 2023)

Metabolomics during the spontaneous fermentation in cocoa (Theobroma cacao L.): An exploraty review - César R. Balcázar-Zumaeta; Efraín M. Castro-Alayo; Ilse S. Cayo-Colca; Guillermo Idrogo-Vásquez; Lucas D. Muñoz-Astecker (Food Research International, 2023)

Risk scores’ performance and their impact on operative decision-making in left-sided endocarditis: a cohort study - A. Fernández-Cisneros; M. Hernández-Meneses; J. Llopis; E. Sandoval; D. Pereda; J. Alcocer; C. Barriuso; M. Castellá; J. Ambrosioni; J. M. Pericàs; B. Vidal; C. Falces; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
The accuracy of contemporary risk scores in predicting perioperative mortality in infective endocarditis (IE) remains controversial. The aim is to evaluate the performance of existent mortality risk scores for cardiovascular surgery in IE and the impact on operability at high-risk thresholds. A single-center retrospective review of adult patients diagnosed with acute left-sided IE undergoing surgery from May 2014 to August 2019 ( n = 142) was done. Individualized risk calculation was obtained according to the available mortality risk scores: EuroScore I and II, PALSUSE, Risk-E, Costa, De Feo-Cotrufo, AEPEI, STS-risk, STS-IE, APORTEI, and ICE-PCS scores. A cross-validation analysis was performed on the score with the best area under the curve (AUC). The 30-day survival was 96.5% (95%CI 91–98%). The score with worse area under the curve (AUC = 0.6) was the STS-IE score, while the higher was for the RISK-E score (AUC = 0.89). The AUC of the majority of risk scores suggested acceptable performance; however, statistically significant differences in expected versus observed mortalities were common. The cross-validation analysis showed that a large number of survivors (> 75%) would not have been operated if arbitrary high-risk threshold estimates had been used to deny surgery. The observed mortality in our cohort is significantly lower than is predicted by contemporary risk scores. Despite the reasonable numeric performance of the analyzed scores, their utility in judging the operability of a given patient remains questionable, as demonstrated in the cross-validation analysis. Future guidelines may advise that denial of surgery should only follow a highly experienced Endocarditis Team evaluation.

Bacterial pathogens’ screening in Brazilian chigger mites (Trombidiformes: Trombiculidae), with the first report of 'Candidatus Rickettsia colombianensi'-like in avian-associated chiggers - Ricardo Bassini-Silva; Fernando de Castro Jacinavicius; Sebastián Muñoz-Leal; Ralph Maturano; Julia Carvalho Takatsu; Graziela Virginia Tolesano-Pascoli; Renata D. Alquezar; Camile Lugarini; Ariane Ferreira; Luciano Moreira-Lima; Cal Welbourn; Ronald Ochoa; et al. (Archives of Microbiology, 2023)

Elevation drives taxonomic, functional and phylogenetic β‐diversity of phyllostomid bats in the Amazon biome - William Douglas Carvalho; Isadora E. Fluck; Isaí Jorge de Castro; Renato Richard Hilário; Ana Carolina Moreira Martins; José Júlio de Toledo; Bruna da Silva Xavier; Cristian Dambros; Paulo E. D. Bobrowiec (Journal of Biogeography, 2023)
Aim We evaluated the relative importance of geographical and environment variables for taxonomic, phylogenetic and functional β‐diversity of phyllostomid bats along the entire Amazon biome and specifically in the lowlands. Location Amazon biome. Taxon Chiroptera. Methods We carried out a bibliographic review and compiled a wide and unprecedented database of 106 phyllostomid bat species at 102 sites throughout the Amazon biome. For all possible pairs of sites in both datasets, we estimated the Jaccard pairwise dissimilarity, that is, β‐diversity, considering its three dimensions—taxonomic, phylogenetic and functional—for its two components—turnover (substitution of species) and differences in species richness. The association between dissimilarity measurements and geographical and environment variables was assessed using multiple regressions on distance matrices (MRM). Results We found that turnover and differences in species richness had similar contributions to the taxonomic β‐diversity. However, for phylogenetic and functional β‐diversity, lineages and functions richness differences contribute slightly more than turnover for total β‐diversity. In the lowlands, species, lineages and functions richness differences were slightly higher than turnover for all diversity dimensions. When accounting for all the sites, elevation was the main predictor of phyllostomid bats' taxonomic, phylogenetic and functional turnover. For lowland sites, ecoregions was the main (but relatively weak) predictor associated with all β‐diversity dimensions. Main conclusions Analysis of filtering sites according to elevation revealed that species in the Amazonian lowlands are taxonomically and phylogenetically different from species in the Andes, and present taxonomic, phylogenetic and functional redundancy between assemblages. When accounting for the whole range of distribution of bats, results showed the predominant effect of elevation over other geographical and environmental predictors. This indicates that the diversity of good dispersers such as bats is more affected by specialisation along environment and climatic gradients than by geographical barriers throughout the Amazon biome.

Neuroprotective Effect of Exogenous Galectin-1 in Status Epilepticus - Amanda Larissa Dias Pacheco; Igor Santana de Melo; Maisa de Araujo Costa; Mariah Morais Celestino Amaral; Nívea Karla de Gusmão Taveiros Silva; Yngrid Mickaelli Oliveira Santos; Daniel Leite Góes Gitaí; Marcelo Duzzioni; Alexandre Urban Borbely; Robinson Sabino Silva; Ana Luiza Ferreira Donatti; Luisa Mestriner; et al. (Molecular Neurobiology, 2022)

Physicochemical and computational analysis of the melamine resin derivative for the glyphosate absorption from water using Langmuir-type model - L. Morales-Quintana; D. Bustos; J. Gallego; O. Valdes; L. Guzmán; F. M. Nachtigall; A. Marican; E. W. Hernández-Rodríguez; F. Avila-Salas; W. Bueno-Silva; L. S. Santos; R. I. Castro (International Journal of Environmental Science and Technology, 2022)

Predicting in vitro fertilization success in the Brazilian public health system: a machine learning approach - Nayara C. N. Barreto; Giulia Z. Castro; Ramon G. Pereira; Francisco A. N. Pereira; Fernando M. Reis; Wagner M. Junior; Ines K. D. Cavallo; Karina B. Gomes (Medical & Biological Engineering & Computing, 2022)

Mercury and Cadmium Concentrations in Muscle Tissue of the Blue Shark (Prionace glauca) in the Central Eastern Pacific Ocean - Rubén D. Castro-Rendón; Marcos D. Calle-Morán; Isabel García-Arévalo; Alfredo Ordiano-Flores; Felipe Galván-Magaña (Biological Trace Element Research, 2022)

Review: Hydrogeology of Northern Mendoza (Argentina), from the Andes to the eastern plains, in the context of climate change - Maria Laura Gomez; G. Hoke; S. D’Ambrosio; S. Moreiras; A. Castro (Hydrogeology Journal, 2022)

Do CMIP models capture long-term observed annual precipitation trends? - S. M. Vicente-Serrano; R. García-Herrera; D. Peña-Angulo; M. Tomas-Burguera; F. Domínguez-Castro; I. Noguera; N. Calvo; C. Murphy; R. Nieto; L. Gimeno; J. M. Gutierrez; C. Azorin-Molina; et al. (Climate Dynamics, 2022)
This study provides a long-term (1891–2014) global assessment of precipitation trends using data from two station-based gridded datasets and climate model outputs evolved through the fifth and sixth phases of the Coupled Model Intercomparison Project (CMIP5 and CMIP6, respectively). Our analysis employs a variety of modeling groups that incorporate low- and high-top level members, with the aim of assessing the possible effects of including a well-resolved stratosphere on the model’s ability to reproduce long-term observed annual precipitation trends. Results demonstrate that only a few regions show statistically significant differences in precipitation trends between observations and models. Nevertheless, this pattern is mostly caused by the strong interannual variability of precipitation in most of the world regions. Thus, statistically significant model-observation differences on trends (1891–2014) are found at the zonal mean scale. The different model groups clearly fail to reproduce the spatial patterns of annual precipitation trends and the regions where stronger increases or decreases are recorded. This study also stresses that there are no significant differences between low- and high-top models in capturing observed precipitation trends, indicating that having a well-resolved stratosphere has a low impact on the accuracy of precipitation projections.

Nanotechnology-Driven Cell-Based Therapies in Regenerative Medicine - D. Alzate-Correa; W. R. Lawrence; A. Salazar-Puerta; N. Higuita-Castro; D. Gallego-Perez (The AAPS Journal, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Megabenthic communities distributed in the outer margins of the Yucatan shelf and their relationship to environmental variables - J Rubio-Polania; D Torruco-Gómez; A González-Solís; R Rodríguez-Canul; M Améndola-Pimenta; I Mariño-Tapia; J Herrera-Silveira; F Árcega-Cabrera; V Ceja-Moreno; J Romo-Alvarado; I Lizarraga-Castro; C Gutiérrez-Solís (Marine Biology Research, 2022)

Ant diversity studies in Brazil: an overview of the myrmecological research in a megadiverse country - F. A. Schmidt; C. R. Ribas; R. M. Feitosa; F. B. Baccaro; A. C. M. de Queiroz; T. G. Sobrinho; Y. Quinet; K. S. Carvalho; T. Izzo; M. S. de Castro Morini; A. Nogueira; H. M. Torezan-Silingardi; et al. (Insectes Sociaux, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Addition of proteinase K during the culture alter the physiology of Bacillus thuringiensis culture and the cry1Ac, nprX, nprA, and spo0A gene transcription - Miguel A. Peña-Rico; Humberto R. Bravo-D; Crisanto Roldan-Sabino; Karla V. Castro-Cerritos; Ariana Huerta-Heredia; A. Karin Navarro-Mtz (Antonie van Leeuwenhoek, 2022)

Evaluation of Bacillus spp. isolates as potential biocontrol agents against charcoal rot caused by Macrophomina phaseolina on common bean - Yolani de J. Bojórquez-Armenta; Guadalupe A. Mora-Romero; Melina López-Meyer; Ignacio E. Maldonado-Mendoza; Claudia Castro-Martínez; Cecilia de los A. Romero-Urías; Jesús D. Cordero-Ramírez; Juan C. Martínez-Álvarez (Journal of General Plant Pathology, 2021)

Effect of salinity on growth, survival, and serum osmolality of red snapper, Lutjanus campechanus - Harsha S. C. Galkanda-Arachchige; Robert P. Davis; Sidra Nazeer; Leonardo Ibarra-Castro; D. Allen Davis (Fish Physiology and Biochemistry, 2021)

Global forest restoration opportunities to foster coral reef conservation - Andrés F. Suárez‐Castro; Hawthorne L. Beyer; Caitlin D. Kuempel; Simon Linke; Pasquale Borrelli; Ove Hoegh‐Guldberg (Global Change Biology, 2021)
Sediment runoff from disturbed coastal catchments is a major threat to marine ecosystems. Understanding where sediments are produced and where they are delivered enables managers to design more effective strategies for improving water quality. A management strategy is targeted restoration of degraded terrestrial areas, as it provides opportunities to reduce land‐based runoff from coastal areas and consequently foster coral reef conservation. To do this strategically, a systematic approach is needed to identify watersheds where restoration actions will provide the highest conservation benefits for coral reefs. Here, we develop a systematic approach for identifying global forest restoration opportunities that would also result in large decreases in the flux of sediments to coral reefs. We estimate how land‐use change affects sediment runoff globally using high‐resolution spatial data and determine the subsequent risk of sediment exposure on coral reefs using a diffusion‐based ocean transport model. Our results reveal that sediment export is a major issue affecting 41% of coral reefs globally. The main coastal watersheds with the highest sediment export are predominantly located in Southeast Asian countries, with Indonesia and the Philippines accounting for 52% of the sediment export in coastal areas near coral reefs. We show how restoring forest across multiple watersheds could help to reduce sediment export to 63,000 km 2 of coral reefs. Although reforestation opportunities in areas that discharge onto coral reefs are relatively small across watersheds, it is possible to achieve large sediment reduction benefits by strategically targeting watersheds located in regions with a high density of corals near to the coast. Thus, reforestation benefits on coral reefs do not necessarily come from the watersheds that produce the highest sediment export. These analyses are key for generating informed action to support both international conservation policy and national restoration activities.

Correction to: Taxonomic, functional and phylogenetic bat diversity decrease from more to less complex natural habitats in the Amazon - William Douglas Carvalho; Karen Mustin; Fábio Z. Farneda; Isaí Jorge de Castro; Renato R. Hilário; Ana Carolina Moreira Martins; João D. Miguel; Bruna da Silva Xavier; José Júlio de Toledo (Oecologia, 2021)

Taxonomic, functional and phylogenetic bat diversity decrease from more to less complex natural habitats in the Amazon - William Douglas Carvalho; Karen Mustin; Fábio Z. Farneda; Isaí Jorge de Castro; Renato R. Hilário; Ana Carolina Moreira Martins; João D. Miguel; Bruna da Silva Xavier; José Júlio de Toledo (Oecologia, 2021)

Predictive factors, outcomes, and molecular epidemiology of Clostridioides difficile diarrhea in Brazilian hospitals - Evelyne Santana Girão; Bruno de Melo Tavares; Sania Alves dos Santos; Gessica Lorena Gamarra; Camila Rizek; Roberta Cristina Martins; Lauro Vieira Perdigão Neto; Constancia Diogo; Tatiana D’ Annibale Orsi; Hugo Manuel Paz Morales; Keite da Silva Nogueira; Adriane Ceshin Maestri; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Cecropia hololeuca : A new source of compounds with potential anti-inflammatory action - Emanuelle G. Machado; Oswaldo Cardoso; Nerilson M. Lima; Paloma E. Carvalho; Alice D. Barbosa; Guilherme F. S. Sobrinho; Jennifer F. Duarte; Laryssa R. Coelho; Pietra P. C. Soares; Ayane G. Orneles; Ana Carolina B. Santos; Kamila B. Santos; et al. (Natural Product Research, 2021)

Association of NFκβ, TNFα, IL-6, IL-1β, and LPL Polymorphisms with Type 2 Diabetes Mellitus and Biochemical Parameters in a Mexican Population - O. C. Martínez-Ramírez; D. A. Salazar-Piña; Ramos-García M. de Lorena; C. Castro-Hernández; L. Casas-Ávila; J. A. Portillo-Jacobo; J. Rubio (Biochemical Genetics, 2021)

Reactive Orange 16 dye degradation in anaerobic and aerobic MBBR coupled with ozonation: addressing pathways and performance - F. D. Castro; J. P. Bassin; T. L. M. Alves; G. L. Sant’Anna; M. Dezotti (International Journal of Environmental Science and Technology, 2021)

The hidden curve behind COVID-19 outbreak: the impact of delay in treatment initiation in cancer patients and how to mitigate the additional risk of dying—the head and neck cancer model - Leandro L. Matos; Carlos Henrique Q. Forster; Gustavo N. Marta; Gilberto Castro Junior; John A. Ridge; Daisy Hirata; Adalberto Miranda-Filho; Ali Hosny; Alvaro Sanabria; Vincent Gregoire; Snehal G. Patel; Johannes J. Fagan; et al. (Cancer Causes & Control, 2021)

Revisiting the paradigm of shark‐driven trophic cascades in coral reef ecosystems - Amelia A. Desbiens; George Roff; William D. Robbins; Brett M. Taylor; Carolina Castro‐Sanguino; Alexandra Dempsey; Peter J. Mumby (Ecology, 2021)
Global overfishing of higher‐level predators has caused cascading effects to lower trophic levels in many marine ecosystems. On coral reefs, which support highly diverse food webs, the degree to which top‐down trophic cascades can occur remains equivocal. Using extensive survey data from coral reefs across the relatively unfished northern Great Barrier Reef (nGBR), we quantified the role of reef sharks in structuring coral reef fish assemblages. Using a structural equation modeling (SEM) approach, we explored the interactions between shark abundance and teleost mesopredator and prey functional group density and biomass, while explicitly accounting for the potentially confounding influence of environmental variation across sites. Although a fourfold difference in reef shark density was observed across our survey sites, this had no impact on either the density or biomass of teleost mesopredators or prey, providing evidence for a lack of trophic cascading across nGBR systems. Instead, many functional groups, including sharks, responded positively to environmental drivers. We found reef sharks to be positively associated with habitat complexity. In turn, physical processes such as wave exposure and current velocity were both correlated well with multiple functional groups, reflecting how changes to energetic conditions and food availability, or modification of habitat affect fish distribution. The diversity of species within coral reef food webs and their associations with bottom‐up drivers likely buffers against trophic cascading across GBR functional guilds when reef shark assemblages are depleted, as has been demonstrated in other complex ecosystems.

Limonium mucronatum : plant communities and cytogenetic characterization of an endemic of the Moroccan Atlantic Coast - Laila Rhazi; Ana Rita Rebelo; Ana S. Róis; Sílvia Castro; João Loureiro; Mohammed El Madihi; Ana Paula Paes; Patrick Grillas; Mohammed Ibn Tattou; Ana D. Caperta (Plant Biosystems, 2021)

Application of rhamnolipid surfactant for remediation of toxic metals of long- and short-term contamination sites - C. S. C. Lopes; D. B. Teixeira; B. F. Braz; R. E. Santelli; L. V. A. de Castilho; J. G. C. Gomez; R. P. V. Castro; L. Seldin; D. M. G. Freire (International Journal of Environmental Science and Technology, 2021)

Effects of Environmental Variables and Habitat Integrity on the Structure of the Aquatic Insect Communities of Streams in the Cerrado-Caatinga Ecotone in Northeastern Brazil - E. R. Castro; D. S. Veras; G. S. Lustosa; C. A. S. Azevêdo; L. Juen (Neotropical Entomology, 2021)

Rutin improves glutamate uptake and inhibits glutamate excitotoxicity in rat brain slices - Rafael S. Ferreira; Jéssica Teles-Souza; Cleide dos Santos Souza; Érica P. L. Pereira; Fillipe M. de Araújo; Alessandra Bispo da Silva; Juliana H. Castro e Silva; Yasmine Nonose; Yanier Núñez-Figueredo; Adriano M. de Assis; Diogo O. Souza; Maria de Fátima D. Costa; et al. (Molecular Biology Reports, 2021)

Recent developments combining ensemble smoother and deep generative networks for facies history matching - Smith W. A. Canchumuni; Jose D. B. Castro; Júlia Potratz; Alexandre A. Emerick; Marco Aurélio C. Pacheco (Computational Geosciences, 2021)

Implications of the temporal variations of geoid heights over South American vertical reference frames - Henry D. Montecino Castro; Silvio Rogerio C. de Freitas (Arabian Journal of Geosciences, 2021)

Morphological damage in Sertoli, myoid and interstitial cells in a mouse model of mucopolysaccharidosis type I (MPS I) - Cinthia Castro do Nascimento; Odair Aguiar; Gustavo Monteiro Viana; Vânia D’Almeida (Molecular Biology Reports, 2021)

An interdisciplinary assessment of private conservation areas in the Western United States - Cristina Quintas-Soriano; Dainee M. Gibson; Jodi S. Brandt; María D. López-Rodríguez; Javier Cabello; Pedro A. Aguilera; Antonio J. Castro (Ambio, 2021)
Conservation easements are the fastest growing private conservation strategy in the United States. However, mechanisms to assess private land conservation as well as their support by the general public are not well understood. This study uses the ecosystem services framework for assessing existing private lands in Idaho and identifies areas for future conservation easements. Using conservation targets of the land trust as a guide for selecting ecosystem services, we (a) mapped the spatial delivery of conservation targets across public and private lands, (b) explored public awareness in terms of social importance and vulnerability, and (c) mapped future priority areas by characterizing conservation bundles. We found that public lands provided the highest levels of conservation targets, and we found no difference in conservation target provision between private areas and conservation easements. The spatial characterization of conservation target bundles identified potential future priority areas for conservation easements, which can guide planning of land trust conservation efforts.

Proximal sensors for monitoring seasonal changes of feeding sites selected by grazing ewes - João Serrano; E. Sales-Baptista; Shakib Shahidian; J. Marques da Silva; I. Ferraz de Oliveira; J. Lopes de Castro; Alfredo Pereira; M. Cancela d’Abreu; Mário de Carvalho (Agroforestry Systems, 2021)

Insights on Zika virus envelope gene conservation in American outbreaks - Mateus V. Thomazella; Quirino A. Lima Neto; Francisco F. Duarte Junior; Fernando A. Jorge; Déborah de Castro Moreira; Amauri D. Leal Junior; Mayra M. Presibella; Irina N. Riediger; Rafael A. da Silva; Isabel Maria V. G. de Carvalho; Dennis A. Bertolini (Brazilian Journal of Microbiology, 2020)

Substance use initiation and the prediction of subsequent academic achievement - Alejandro D. Meruelo; Norma Castro; Tam Nguyen-Louie; Susan F. Tapert (Brain Imaging and Behavior, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Delinted cottonseed in diets for finishing sheep - W. J. R. Castro; A. M. Zanine; D. J. Ferreira; A. L. Souza; R. M. A. Pinho; M. O. M. Parente; H. N. Parente; E. M. Santos (Tropical Animal Health and Production, 2020)

Latitudinal patterns of species diversity on South American rocky shores: Local processes lead to contrasting trends in regional and local species diversity - Juan J. Cruz‐Motta; Patricia Miloslavich; Edlin Guerra‐Castro; Alejandra Hernández‐Agreda; Cesar Herrera; Francisco Barros; Sergio A. Navarrete; Roger D. Sepúlveda; Tim M. Glasby; Gregorio Bigatti; Maritza Cardenas‐Calle; Pedro B. M. Carneiro; et al. (Journal of Biogeography, 2020)
Aim We evaluated whether patterns of species diversity (α, β and γ) of rocky shore assemblages followed latitudinal gradients (i.e. LDGs) along the South American coasts, and tested hypotheses related to potential processes sustaining or disrupting the expected LDG pattern at various spatial scales. Location Coasts of South America. Taxon Macroalgae and sessile/slow‐moving macrofauna on intertidal rocky shores. Methods We evaluated changes in species composition across 143 sites. The degree of replacement and loss of species at different spatial scales (i.e. coasts, regions and sites) were estimated to help distinguish among ecological, historical and evolutionary hypotheses for explaining LDGs. Furthermore, components of diversity and taxonomic distinctness were measured, and variability in these measures was decomposed using analysis of covariance. Finally, we examined relationships between diversity and a suite of environmental and anthropogenic variables to identify potential mechanisms that may be responsible for the reported spatial relationships. Results Species composition varied with latitude, and this variability was relatively consistent on both coasts. At all spatial scales, replacement of species was the dominant phenomenon (>95%), rather than loss in the total number of species ( Main conclusions Species diversity of South American rocky shores followed, with interruptions, LDGs. The trend of those LDGs, however, depended on the scale and metric used to describe diversity. It is proposed that patterns of LDGs at various scales are not the result of a single overarching process but are strongly influenced by local and regional processes. Although the most evident environmental gradient was the decrease in SST towards the south, it was demonstrated that regional and local environmental variables were also important for understanding the increase in regional β‐diversity towards the tropics.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Nutritional evaluation and human health-promoting potential of compounds biosynthesized by native microalgae from the Peruvian Amazon - Marianela Cobos; Sheyla Pérez; Janeth Braga; Gabriel Vargas-Arana; Leenin Flores; Jae D. Paredes; J. Dylan Maddox; Jorge L. Marapara; Juan C. Castro (World Journal of Microbiology and Biotechnology, 2020)

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

New Aspects of VEGF, GABA, and Glutamate Signaling in the Neocortex of Human Temporal Lobe Pharmacoresistant Epilepsy Revealed by RT-qPCR Arrays - Rubén D. Castro-Torres; Mónica E. Ureña-Guerrero; Lilia M. Morales-Chacón; Lourdes Lorigados-Pedre; Bárbara Estupiñan-Díaz; Luisa Rocha; Sandra Orozco-Suárez; Martha C. Rivera-Cervantes; Mario Alonso-Vanegas; Carlos Beas-Zárate (Journal of Molecular Neuroscience, 2020)

A Global Review of Ligustrum Lucidum (OLEACEAE) Invasion - Romina D. Fernandez; Sergio J. Ceballos; Roxana Aragón; Agustina Malizia; Lía Montti; Juan I. Whitworth-Hulse; Pilar Castro-Díez; H. Ricardo Grau (The Botanical Review, 2020)

Polymorphism in Conservative Structures? The Scapulocoracoids in Skates Genus Psammobatis (Chondrichthyes, Arhynchobatidae) and the Validity of P. parvacauda - E. Mabragaña; M. González-Castro; V. Gabbanelli; D. M. Vazquez; J. M. Díaz de Astarloa (Frontiers in Marine Science, 2020)

Morphologic description of male reproductive accessory glands in a mouse model of mucopolysaccharidosis type I (MPS I) - Cinthia Castro do Nascimento; Odair Aguiar Junior; Vânia D’Almeida (Journal of Molecular Histology, 2020)

Oxidative stress resistance in a short-lived Neotropical annual killifish - Robson S. Godoy; Luis Esteban K. Lanés; Bruna D. Castro; Vinicius Weber; Natália Wingen; Mateus M. Pires; Guendalina T. Oliveira; Leonardo Maltchik (Biogerontology, 2020)

A comparison of machine and deep-learning algorithms applied to multisource data for a subtropical forest area classification - C. Sothe; C. M. De Almeida; M. B. Schimalski; V. Liesenberg; L. E. C. La Rosa; J. D. B. Castro; R. Q. Feitosa (International Journal of Remote Sensing, 2020)

Populations of Populus angustifolia have evolved distinct metabolic profiles that influence their surrounding soil - Liam O. Mueller; Samuel R. Borstein; Eric D. Tague; Stephen P. Dearth; Hector F. Castro; Shawn R. Campagna; Joseph K. Bailey; Jennifer A. Schweitzer (Plant and Soil, 2020)

Combined effects of land-use intensification and plant invasion on native communities - C. Gutiérrez-Cánovas; D. Sánchez-Fernández; P. González-Moreno; E. Mateos-Naranjo; P. Castro-Díez; M. Vilà (Oecologia, 2020)

Acidithiobacillus ferrianus sp. nov.: an ancestral extremely acidophilic and facultatively anaerobic chemolithoautotroph - Paul R. Norris; Carmen Falagán; Ana Moya-Beltrán; Matías Castro; Raquel Quatrini; D. Barrie Johnson (Extremophiles, 2020)
Strain MG, isolated from an acidic pond sediment on the island of Milos (Greece), is proposed as a novel species of ferrous iron- and sulfur-oxidizing Acidithiobacillus . Currently, four of the eight validated species of this genus oxidize ferrous iron, and strain MG shares many key characteristics with these four, including the capacities for catalyzing the oxidative dissolution of pyrite and for anaerobic growth via ferric iron respiration. Strain MG also grows aerobically on hydrogen and anaerobically on hydrogen coupled to ferric iron reduction. While the 16S rRNA genes of the iron-oxidizing Acidi-thiobacillus species (and strain MG) are located in a distinct phylogenetic clade and are closely related (98–99% 16S rRNA gene identity), genomic relatedness indexes (ANI/dDDH) revealed strong genomic divergence between strain MG and all sequenced type strains of the taxon, and placed MG as the first cultured representative of an ancestral phylotype of iron oxidizing acidithiobacilli. Strain MG is proposed as a novel species, Acidithiobacillus ferrianus sp. nov. The type strain is MG T (= DSM 107098 T = JCM 33084 T ). Similar strains have been found as isolates or indicated by cloned 16S rRNA genes from several mineral sulfide mine sites.

Assessment of yield gaps on global grazed‐only permanent pasture using climate binning - Leonardo A. Monteiro; Andrew M. Allee; Eleanor E. Campbell; Lee R. Lynd; Johnny R. Soares; Deepak Jaiswal; Julianne de Castro Oliveira; Murilo dos Santos Vianna; Ashley E. Morishige; Gleyce K. D. A. Figueiredo; Rubens A. C. Lamparelli; Nathaniel D. Mueller; et al. (Global Change Biology, 2020)
To meet rising demands for agricultural products, existing agricultural lands must either produce more or expand in area. Yield gaps (YGs)—the difference between current and potential yield of agricultural systems—indicate the ability to increase output while holding land area constant. Here, we assess YGs in global grazed‐only permanent pasture lands using a climate binning approach. We create a snapshot of circa 2000 empirical yields for meat and milk production from cattle, sheep, and goats by sorting pastures into climate bins defined by total annual precipitation and growing degree‐days. We then estimate YGs from intra‐bin yield comparisons. We evaluate YG patterns across three FAO definitions of grazed livestock agroecosystems (arid, humid, and temperate), and groups of animal production systems that vary in animal types and animal products. For all subcategories of grazed‐only permanent pasture assessed, we find potential to increase productivity several‐fold over current levels. However, because productivity of grazed pasture systems is generally low, even large relative increases in yield translated to small absolute gains in global protein production. In our dataset, milk‐focused production systems were found to be seven times as productive as meat‐focused production systems regardless of animal type, while cattle were four times as productive as sheep and goats regardless of animal output type. Sustainable intensification of pasture is most promising for local development, where large relative increases in production can substantially increase incomes or “spare” large amounts of land for other uses. Our results motivate the need for further studies to target agroecological and economic limitations on productivity to improve YG estimates and identify sustainable pathways toward intensification.

Characterization of lapachol cytotoxicity: contribution of glutathione depletion for oxidative stress in Saccharomyces cerevisiae - Frederico A. V. Castro; Gabriel F. M. de Souza; Marcos D. Pereira (Folia Microbiologica, 2020)

A satellite algorithm for estimating relative humidity, based on GOES and MODIS satellite data - Nazario D. Ramírez- Beltrán; Cesar M. Salazar; Joan M. Castro Sánchez; Jorge E. González (International Journal of Remote Sensing, 2019)

The worm burden of tracer kids and lambs browsing heterogeneous vegetation is influenced by strata harvested and not total dry matter intake or plant life form - P. R. Jaimez-Rodríguez; P. G. González-Pech; J. Ventura-Cordero; D. R. B. Brito; L. M. Costa-Júnior; C. A. Sandoval-Castro; J. F. J. Torres-Acosta (Tropical Animal Health and Production, 2019)

A nongenomic mechanism for “metalloestrogenic” effects of cadmium in human uterine leiomyoma cells through G protein-coupled estrogen receptor - Jingli Liu; Linda Yu; Lysandra Castro; Yitang Yan; Maria I. Sifre; Carl D. Bortner; Darlene Dixon (Archives of Toxicology, 2019)

Drought decreases incorporation of recent plant photosynthate into soil food webs regardless of their trophic complexity - Mathilde Chomel; Jocelyn M. Lavallee; Nil Alvarez‐Segura; Francisco de Castro; Jennifer M. Rhymes; Tancredi Caruso; Franciska T. de Vries; Elizabeth M. Baggs; Mark C. Emmerson; Richard D. Bardgett; David Johnson (Global Change Biology, 2019)
Theory suggests that more complex food webs promote stability and can buffer the effects of perturbations, such as drought, on soil organisms and ecosystem functions. Here, we tested experimentally how soil food web trophic complexity modulates the response to drought of soil functions related to carbon cycling and the capture and transfer below‐ground of recent photosynthate by plants. We constructed experimental systems comprising soil communities with one, two or three trophic levels (microorganisms, detritivores and predators) and subjected them to drought. We investigated how food web trophic complexity in interaction with drought influenced litter decomposition, soil CO 2 efflux, mycorrhizal colonization, fungal production, microbial communities and soil fauna biomass. Plants were pulse‐labelled after the drought with 13 C‐CO 2 to quantify the capture of recent photosynthate and its transfer below‐ground. Overall, our results show that drought and soil food web trophic complexity do not interact to affect soil functions and microbial community composition, but act independently, with an overall stronger effect of drought. After drought, the net uptake of 13 C by plants was reduced and its retention in plant biomass was greater, leading to a strong decrease in carbon transfer below‐ground. Although food web trophic complexity influenced the biomass of Collembola and fungal hyphal length, 13 C enrichment and the net transfer of carbon from plant shoots to microbes and soil CO 2 efflux were not affected significantly by varying the number of trophic groups. Our results indicate that drought has a strong effect on above‐ground–below‐ground linkages by reducing the flow of recent photosynthate. Our results emphasize the sensitivity of the critical pathway of recent photosynthate transfer from plants to soil organisms to a drought perturbation, and show that these effects may not be mitigated by the trophic complexity of soil communities, at least at the level manipulated in this experiment.

Optical properties of atmospheric particles over an urban site in Mexico City and a peri-urban site in Queretaro - Rafael N. Liñán-Abanto; O. Peralta; D. Salcedo; L. G. Ruiz-Suárez; P. Arnott; G. Paredes-Miranda; H. Alvarez-Ospina; T. Castro (Journal of Atmospheric Chemistry, 2019)

JNK Isoforms Are Involved in the Control of Adult Hippocampal Neurogenesis in Mice, Both in Physiological Conditions and in an Experimental Model of Temporal Lobe Epilepsy - Rubén D. Castro-Torres; Jon Landa; Marina Rabaza; Oriol Busquets; Jordi Olloquequi; Miren Ettcheto; Carlos Beas-Zarate; Jaume Folch; Antoni Camins; Carme Auladell; Ester Verdaguer (Molecular Neurobiology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

The Impact of the Right Coronary Artery Geometric Parameters on Hemodynamic Performance - N. Pinho; L. C. Sousa; C. F. Castro; C. C. António; M. Carvalho; W. Ferreira; R. Ladeiras-Lopes; N. D. Ferreira; P. Braga; N. Bettencourt; S. I. S. Pinto (Cardiovascular Engineering and Technology, 2019)

Citalopram Reduces Aggregation of ATXN3 in a YAC Transgenic Mouse Model of Machado-Joseph Disease - Naila S. Ashraf; Sara Duarte-Silva; Emily D. Shaw; Patrícia Maciel; Henry L. Paulson; Andreia Teixeira-Castro; Maria do Carmo Costa (Molecular Neurobiology, 2019)

Two New Species of the Spittlebug Genus Ocoaxo Fennah (Hemiptera: Cercopidae) from Mexico, and Keys for the Groups, Group Three, and First Subgroup - U Castro-Valderrama; G S Carvalho; D C Peck; J M Valdez-Carrasco; J Romero Nápoles (Neotropical Entomology, 2019)

Art Museums: a Good Context for Outreach Activities on Natural Stones and Heritage - D. Pereira; P. Perez-Castro (Geoheritage, 2019)

Anti-obesity effects of kaempferol by inhibiting adipogenesis and increasing lipolysis in 3T3-L1 cells - D. Torres-Villarreal; A. Camacho; H. Castro; R. Ortiz-Lopez; A. L. de la Garza (Journal of Physiology and Biochemistry, 2019)

Exploring drivers of litter decomposition in a greening Arctic: results from a transplant experiment across a treeline - Thomas C. Parker; Jonathan Sanderman; Robert D. Holden; Gesche Blume‐Werry; Sofie Sjögersten; David Large; Miguel Castro‐Díaz; Lorna E. Street; Jens‐Arne Subke; Philip A. Wookey (Ecology, 2018)
Decomposition of plant litter is a key control over carbon (C) storage in the soil. The biochemistry of the litter being produced, the environment in which the decomposition is taking place, and the community composition and metabolism of the decomposer organisms exert a combined influence over decomposition rates. As deciduous shrubs and trees are expanding into tundra ecosystems as a result of regional climate warming, this change in vegetation represents a change in litter input to tundra soils and a change in the environment in which litter decomposes. To test the importance of litter biochemistry and environment in determining litter mass loss, we reciprocally transplanted litter between heath ( Empetrum nigrum ), shrub ( Betula nana ), and forest ( Betula pubescens ) at a sub‐Arctic treeline in Sweden. As expansion of shrubs and trees promotes deeper snow, we also used a snow fence experiment in a tundra heath environment to understand the importance of snow depth, relative to other factors, in the decomposition of litter. Our results show that B. pubescens and B. nana leaf litter decomposed at faster rates than E. nigrum litter across all environments, while all litter species decomposed at faster rates in the forest and shrub environments than in the tundra heath. The effect of increased snow on decomposition was minimal, leading us to conclude that microbial activity over summer in the productive forest and shrub vegetation is driving increased mass loss compared to the heath. Using B. pubescens and E. nigrum litter, we demonstrate that degradation of carbohydrate‐C is a significant driver of mass loss in the forest. This pathway was less prominent in the heath, which is consistent with observations that tundra soils typically have high concentrations of “labile” C. This experiment suggests that further expansion of shrubs and trees may stimulate the loss of undecomposed carbohydrate C in the tundra.

The Híbrido de Timor germplasm: identification of molecular diversity and resistance sources to coffee berry disease and leaf rust - R. A. Silva; L. Zambolim; I. S. L. Castro; H. S. Rodrigues; C. D. Cruz; E. T. Caixeta (Euphytica, 2018)

Metabolome changes are induced in the arbuscular mycorrhizal fungus Gigaspora margarita by germination and by its bacterial endosymbiont - Stephen P. Dearth; Hector F. Castro; Francesco Venice; Eric D. Tague; Mara Novero; Paola Bonfante; Shawn Robert Campagna (Mycorrhiza, 2018)

Morphotectonic development of the Ceará Terrace: a marginal ridge on the western side of the Romanche Fracture Zone in the Brazilian Equatorial Margin - João Fernando Pezza Andrade; M. P. Gomes; F. H. R. Bezerra; D. L. de Castro; H. Vital (Geo-Marine Letters, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Atorvastatin Prevents Early Oxidative Events and Modulates Inflammatory Mediators in the Striatum Following Intranasal 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) Administration in Rats - Naiani F. Marques; Adalberto A. Castro; Gianni Mancini; Fernanda L. Rocha; Adair R. S. Santos; Rui D. Prediger; Andreza Fabro De Bem; Carla I. Tasca (Neurotoxicity Research, 2018)

Genotoxicity of spent pot liner as determined with the zebrafish (Danio rerio) experimental model - Tássia F. D. Castro; Isadora M. Paiva; Aline F. S. Carvalho; Isadora L. Assis; Marcel J. Palmieri; Larissa F. Andrade-Vieira; Silvana Marcussi; Luis D. Solis-Murgas (Environmental Science and Pollution Research, 2018)

Characterization of biofilm formation by Salmonella enterica at the air-liquid interface in aquatic environments - José Andrés Medrano-Félix; Cristóbal Chaidez; Kristina D. Mena; María del Socorro Soto-Galindo; Nohelia Castro-del Campo (Environmental Monitoring and Assessment, 2018)

Abnormalities in flatfishes of the south‐west Atlantic Ocean - D. L. Castellini; M. González‐Castro; A. Lopez‐Cazorla; J. M. Díaz De Astarloa (Journal of Fish Biology, 2018)
Five adult paralichthyid specimens with various kinds of abnormalities are reported from the south‐west Atlantic Ocean. These abnormal flatfish specimens represent the first records of wholly ambicoloured Paralichthys orbignyanus specimens having a deep notch between the eye and dorsal fin and a partially albinistic specimen having skeletal deformities and only the second record of an almost totally ambicoloured specimen. We also report the first observation of reversal in Paralichthys patagonicus and an almost totally ambicoloured, reversed Xystreurys rasile .

Optimization of water allocation in the Shatt al-Arab River under different salinity regimes and tide impact - Ali D. Abdullah; Mario Erik Castro-Gama; Ioana Popescu; Pieter van der Zaag; Usama Karim; Qusay Al Suhail (Hydrological Sciences Journal, 2018)

First evidence of viral and bacterial oyster pathogens in the Brazilian coast - D F Mello; N M Danielli; F Curbani; V A Pontinha; S Suhnel; M A M Castro; S C Medeiros; N C Wendt; R Trevisan; A R M Magalhães; A L Dafre (Journal of Fish Diseases, 2018)

The future of fish passage science, engineering, and practice - Ana T. Silva; Martyn C. Lucas; Theodore Castro‐Santos; Christos Katopodis; Lee J. Baumgartner; Jason D. Thiem; Kim Aarestrup; Paulo S. Pompeu; Gordon C. O'Brien; Douglas C. Braun; Nicholas J. Burnett; David Z. Zhu; et al. (Fish and Fisheries, 2018)
Much effort has been devoted to developing, constructing and refining fish passage facilities to enable target species to pass barriers on fluvial systems, and yet, fishway science, engineering and practice remain imperfect. In this review, 17 experts from different fish passage research fields (i.e., biology, ecology, physiology, ecohydraulics, engineering) and from different continents (i.e., North and South America, Europe, Africa, Australia) identified knowledge gaps and provided a roadmap for research priorities and technical developments. Once dominated by an engineering‐focused approach, fishway science today involves a wide range of disciplines from fish behaviour to socioeconomics to complex modelling of passage prioritization options in river networks. River barrier impacts on fish migration and dispersal are currently better understood than historically, but basic ecological knowledge underpinning the need for effective fish passage in many regions of the world, including in biodiversity hotspots (e.g., equatorial Africa, South‐East Asia), remains largely unknown. Designing efficient fishways, with minimal passage delay and post‐passage impacts, requires adaptive management and continued innovation. While the use of fishways in river restoration demands a transition towards fish passage at the community scale, advances in selective fishways are also needed to manage invasive fish colonization. Because of the erroneous view in some literature and communities of practice that fish passage is largely a proven technology, improved international collaboration, information sharing, method standardization and multidisciplinary training are needed. Further development of regional expertise is needed in South America, Asia and Africa where hydropower dams are currently being planned and constructed.

Bleaching in reef invertebrate larvae associated with Symbiodinium strains within clades A–F - M. Mies; A. Z. Güth; C. B. Castro; D. O. Pires; E. N. Calderon; M. Pompeu; P. Y. G. Sumida (Marine Biology, 2018)

Vertical deformation and sea level changes in the coast of Chile by satellite altimetry and tide gauges - Henry D. C. Montecino; Vagner G. Ferreira; Aharon Cuevas; Leoncio Castro Cabrera; Juan Carlos Soto Báez; Silvio R. C. De Freitas (International Journal of Remote Sensing, 2017)

Exploring Institutional Mechanisms for Scientific Input into the Management Cycle of the National Protected Area Network of Peru: Gaps and Opportunities - M. D. López-Rodríguez; H. Castro; M. Arenas; J. M. Requena-Mullor; A. Cano; E. Valenzuela; J. Cabello (Environmental Management, 2017)

Production of three symbiosis-related fatty acids by Symbiodinium types in clades A–F associated with marine invertebrate larvae - M. Mies; A. B. Chaves-Filho; S. Miyamoto; A. Z. Güth; A. A. Tenório; C. B. Castro; D. O. Pires; E. N. Calderon; P. Y. G. Sumida (Coral Reefs, 2017)

Plume composition and volatile flux of Nyamulagira volcano, Democratic Republic of Congo, during birth and evolution of the lava lake, 2014–2015 - N. Bobrowski; G. B. Giuffrida; S. Arellano; M. Yalire; M. Liotta; L. Brusca; S. Calabrese; S. Scaglione; J. Rüdiger; J. M. Castro; B. Galle; D. Tedesco (Bulletin of Volcanology, 2017)

Remote Sensing of Seagrass Leaf Area Index and Species: The Capability of a Model Inversion Method Assessed by Sensitivity Analysis and Hyperspectral Data of Florida Bay - John D. Hedley; Brandon J. Russell; Kaylan Randolph; Miguel Á. Pérez-Castro; Román M. Vásquez-Elizondo; Susana Enríquez; Heidi M. Dierssen (Frontiers in Marine Science, 2017)

Short-term and long-term effects of diazepam on the memory for discrimination and generalization of scopolamine - C. Casasola-Castro; L. Weissmann-Sánchez; E. Calixto-González; A. Aguayo-Del Castillo; D. N. Velázquez-Martínez (Psychopharmacology, 2017)

A fucan of a brown seaweed and its antitumoral property on HT-29 and immunomodulatory activity in murine RAW 264.7 macrophage cell line - Thuane de Sousa Pinheiro; Marilia da S. Nascimento Santos; Luiza Sheyla E. P. Will Castro; Almino Afonso de O. Paiva; Luciana G. Alves; Ana Katarina M. Cruz; Leonardo Thiago D. B. Nobre; Monique Gabriela das C. F. Alves; Edda Lisboa Leite (Journal of Applied Phycology, 2017)

Search and analysis of genes involved in antibiotic resistance in Chilean strains of Piscirickettsia salmonis - C Cartes; A Isla; F Lagos; D Castro; M Muñoz; A Yañez; D Haussmann; J Figueroa (Journal of Fish Diseases, 2017)
Piscirickettsia salmonis is the pathogen causing Piscirickettsiosis. For treatment, the industry mainly uses oxytetracycline and florfenicol, so it is essential to understand the degree of susceptibility of this pathogen to these drugs. But this is still unknown for a large number of P. salmonis strains, as are the molecular mechanisms responsible for greater or lesser susceptibility. However, genes that confer resistance to these antimicrobials have been reported and characterized for this and other bacterial species, among which are membrane proteins that take out the drug. Our results identified differences in the degree of susceptibility to both antibiotics among different Chilean isolated of these bacteria. We analysed 10 available genomes in our laboratory and identified ~140 genes likely to be involved in antibiotic resistance. We analysed six specific genes, which suggests that some of them would eventually be relevant in conferring resistance to both antibiotics, as they encode for specific transporter proteins, which increase the number of transcripts when grown in media with these antibiotics. Our results were corroborated with EtBr permeability analysis, which revealed that the LF ‐89 strain accumulates this compound and has a reduced capacity to expulse it compared with the field strains.

Bacteriological and histopathological study of farmed rainbow trout, Oncorhynchus mykiss , in Peru - E C Mateo; T Castro; V Sierralta; D R Mateo (Journal of Fish Diseases, 2017)

Evaluating the predictive power of field variables for species and individual molecular identification on wolf noninvasive samples - Mónia Nakamura; Raquel Godinho; H. Rio-Maior; S. Roque; A. Kaliontzopoulou; J. Bernardo; D. Castro; S. Lopes; F. Petrucci-Fonseca; F. Álvares (European Journal of Wildlife Research, 2017)

Host status of selected cultivated fruit crops to Meloidogyne enterolobii - Vânia M. Freitas; Joelma G. P. Silva; Cesar B. Gomes; José M. C. Castro; Valdir R. Correa; Regina M. D. G. Carneiro (European Journal of Plant Pathology, 2017)

Energy Dissipating Devices in Falling Rock Protection Barriers - L. Castanon-Jano; E. Blanco-Fernandez; D. Castro-Fresno; F. Ballester-Muñoz (Rock Mechanics and Rock Engineering, 2017)

Inactivation, lysis and degradation by-products of Saccharomyces cerevisiae by electrooxidation using DSA - Lyliane F. Trigueiro; Larissa M. Silva; Luciana A. B. D. Itto; Thiago M. B. F. Oliveira; Artur J. Motheo; Carlos A. Martínez-Huitle; Janete J. F. Alves; Suely S. L. Castro (Environmental Science and Pollution Research, 2017)

Treatment of a simulated textile wastewater containing the Reactive Orange 16 azo dye by a combination of ozonation and moving-bed biofilm reactor: evaluating the performance, toxicity, and oxidation by-products - Francine D. Castro; João Paulo Bassin; Márcia Dezotti (Environmental Science and Pollution Research, 2017)

Optimized treatment conditions for textile wastewater reuse using photocatalytic processes under UV and visible light sources - Maria Clara V. M. Starling; Luiz Augusto S. Castro; Rafaela B. P. Marcelino; Mônica M. D. Leão; Camila C. Amorim (Environmental Science and Pollution Research, 2017)

Peripheral and central antinociceptive effects of the butanolic fraction of Byrsonima verbascifolia leaves on nociception-induced models in mice - A. A. Saldanha; J. M. Siqueira; A. H. F. Castro; N. A. Matos; A. Klein; D. B. Silva; C. A. Carollo; A. C. Soares (Inflammopharmacology, 2017)

Measurements and Computations of Flow in an Urban Street System - Ian P. Castro; Zheng-Tong Xie; V. Fuka; Alan G. Robins; M. Carpentieri; P. Hayden; D. Hertwig; O. Coceal (Boundary-Layer Meteorology, 2017)

Synthesis and in vitro evaluation of novel triazole/azide chalcones - Fernanda C. G. Evangelista; Maralice O. Bandeira; Graziele D. Silva; Marina G. Silva; Silmara N. Andrade; Deisielly R. Marques; Luciana M. Silva; Whocely V. Castro; Fabio V. Santos; Gustavo H. R. Viana; José A. F. P. Villar; Adriano P. Sabino; et al. (Medicinal Chemistry Research, 2017)

Challenges in the management of patients with maple syrup urine disease diagnosed by newborn screening in a developing country - Leniza G. De Castro-Hamoy; Mary Anne D. Chiong; Sylvia C. Estrada; Cynthia P. Cordero (Journal of Community Genetics, 2017)

Characterization of hepatitis B virus infection in illicit drug users in the Marajó Archipelago, northern Brazil - Andréia P. Andrade; Suzy D. B. Pacheco; Fabricio Q. Silva; Luiz M. L. Pinheiro; Jairo A. A. Castro; Carlos E. M. Amaral; Renata B. Hermes; Benedikt Fischer; João R. R. Pinho; José Alexandre R. Lemos; Aldemir B. Oliveira-Filho (Archives of Virology, 2017)

Performance and health of Holstein calves fed different levels of milk fortified with symbiotic complex containing pre- and probiotics - M. I. Marcondes; T. R. Pereira; J. C. C. Chagas; E. A. Filgueiras; M. M. D. Castro; G. P. Costa; A. L. L. Sguizzato; R. D. Sainz (Tropical Animal Health and Production, 2016)

Concentrations of Metals, Metalloids, and Chlorinated Pollutants in Blood and Plasma of White Stork (Ciconia ciconia) Nestlings From Spain - M. Pérez-López; I. De la Casa-Resino; D. Hernández-Moreno; J. Galeano; M. P. Míguez-Santiyán; A. de Castro-Lorenzo; M. Otero-Filgueiras; O. Rivas-López; F. Soler (Archives of Environmental Contamination and Toxicology, 2016)

Influence of Mussel Culture on the Vertical Export of Phytoplankton Carbon in a Coastal Upwelling Embayment (Ría de Vigo, NW Iberia) - M. Froján; F. G. Figueiras; D. Zúñiga; F. Alonso-Pérez; B. Arbones; C. G. Castro (Estuaries and Coasts, 2016)

Characterization of Escherichia coli strains from red deer (Cervus elaphus) faeces in a Mexican protected natural area - Mariana D. Carrillo-Del Valle; Jorge A. De la Garza-García; Efrén Díaz-Aparicio; Arturo G. Valdivia-Flores; Luis F. Cisneros-Guzmán; Cecilia Rosario; Ángel H. Manjarrez-Hernández; Armando Navarro; Juan Xicohtencatl-Cortes; Pablo Maravilla; Rigoberto Hernández-Castro (European Journal of Wildlife Research, 2016)

Subaerial biofilms on granitic historic buildings: microbial diversity and development of phototrophic multi-species cultures - D. Vázquez-Nion; J. Rodríguez-Castro; M. C. López-Rodríguez; I. Fernández-Silva; B. Prieto (Biofouling, 2016)

Quality of the Solimões River water for domestic use by the riverine community situated in Manacapuru-Amazonas-Brazil - N. G. P. Pantoja; L. M. Castro; S. D. Rocha; J. A. Silva; J. S. P. Ribeiro; A. R. Donald; L. M. Silva; T. C. S. Oliveira (Environmental Science and Pollution Research, 2016)

Brazilian recreational fisheries: current status, challenges and future direction - K. M. F. Freire; R. A. Tubino; C. Monteiro‐Neto; M. F. Andrade‐Tubino; C. G. Belruss; A. R. G. Tomás; S. L. S. Tutui; P. M. G. Castro; L. S. Maruyama; A. C. Catella; D. V. Crepaldi; C. R. A. Daniel; et al. (Fisheries Management and Ecology, 2016)
Recreational fisheries in Brazil have increased in importance and attracted many foreign recreational fishers. The objectives of this article were to summarise the available data on Brazilian recreational fisheries, to discuss some of their features and to analyse how they are performing in different regions compared with international trends. A review of published and unpublished sources together with data from recreational fishing licences was used. The participation rate was low (0.9%). Overall, there was a high diversity of fish species, with the following species/group of species repeatedly reported: Menticirrhus spp., Centropomus spp., Cynoscion spp., and Micropogonias furnieri (marine/estuarine water), and Cichla spp., Hoplias malabaricus , and Piaractus mesopotamicus , together with the introduced Oreochromis niloticus and Coptodon rendalli (fresh water). The north‐eastern region differs from the other regions: fishing occurs mostly in marine waters and fishers acquire mainly shore‐based licences, have minimum fishing expenditures and rarely release fishes. There is no estimate of the total harvest or economic value. Conflicts include catch‐and‐release‐oriented freshwater and marine recreational fishers vs consumption‐oriented coastal fishers, tournament participants vs non‐participants, commercial fishers and other leisure activities, pollution, ports, species introductions and translocations, protected areas, and federal and state laws. Cases of smooth shifts from artisanal to recreational fishing were detected, possibly associated with changes in the societal relationship with natural resources.

On the Effectiveness of Wastewater Cylindrical Reactors: an Analysis Through Steiner Symmetrization - J. I. Díaz; D. Gómez-Castro (Pure and Applied Geophysics, 2016)

Thyroid hormones improve cardiac function and decrease expression of pro-apoptotic proteins in the heart of rats 14 days after infarction - Alexandre Luz de Castro; Rafael Oliveira Fernandes; Vanessa D. Ortiz; Cristina Campos; Jéssica H. P. Bonetto; Tânia R. G. Fernandes; Adriana Conzatti; Rafaela Siqueira; Angela Vicente Tavares; Paulo Cavalheiro Schenkel; Adriane Belló-Klein; Alex Sander da Rosa Araujo (Apoptosis, 2016)

Impact of HIV infection on sustained virological response to treatment against hepatitis C virus with pegylated interferon plus ribavirin - P. Monje-Agudo; A. Castro-Iglesias; A. Rivero-Juárez; F. Martínez-Marcos; E. Ortega-González; L. M. Real; B. Pernas; N. Merchante; P. Cid; J. Macías; M. D. Merino; A. Rivero; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Regional climate modelling in CLARIS-LPB: a concerted approach towards twentyfirst century projections of regional temperature and precipitation over South America - E. Sánchez; S. Solman; A. R. C. Remedio; H. Berbery; P. Samuelsson; R. P. Da Rocha; C. Mourão; L. Li; J. Marengo; M. de Castro; D. Jacob (Climate Dynamics, 2015)

Isotopic variation in five species of stream fishes under the influence of different land uses - D. R. Carvalho; D. Castro; M. Callisto; M. Z. Moreira; P. S. Pompeu (Journal of Fish Biology, 2015)
The aim of this study was to test if changes in land use alter the isotopic signature of fish species, promoting changes in the trophic position and food resource partitioning between these consumers. Three different systems were investigated: pasture streams ( n = 3), streams in sugar cane plantations ( n = 3) and reference streams ( n = 3). Fish species Aspidoras fuscoguttatus , Astyanax altiparanae , Characidium zebra , Hisonotus piracanjuba and Knodus moenkhausii were selected, and their nitrogen and carbon isotopic compositions were estimated to assess changes in the trophic level and partitioning of food items consumed. The composition of δ 13 C (‰) only differed among the land use categories for A. altiparanae , H. piracanjuba and K. moenkhausii. Resource partitioning was different for all species, with changes in the sources or proportions they consumed in each land use category, but only A. altiparanae introduced new food sources in large quantity in altered land uses. It is important to note, however, that the results from the resource partitioning analysis are limited due to large overlapping of isotopic signatures between the analysed food resources. All fish species exhibited variation in δ 15 N (‰), with the highest values found in streams under sugar cane or pasture influence. Despite the variation in nitrogen isotopic values, only C. zebra and H. piracanjuba displayed changes in trophic level. Therefore, it is believed that the increase in the δ 15 N (‰) value of the individuals collected in streams under the influence of sugar cane or pasture was due to the greater influence of livestock dung and chemical and organic fertilizers. The results also highlight the importance of studying consumer species along with all forms of resources available at each location separately, because the signatures of these resources also vary within different land uses.

Footprints in the sand: a persistent spatial impression of fishing in a mobile groundfish assemblage - Francisco de Castro; Samuel Shephard; Sarah B. M. Kraak; David G. Reid; Keith D. Farnsworth (Marine Biology, 2015)

Assessing the effect of domain size over the Caribbean region using the PRECIS regional climate model - Abel Centella-Artola; Michael A. Taylor; Arnoldo Bezanilla-Morlot; Daniel Martinez-Castro; Jayaka D. Campbell; Tannecia S. Stephenson; Alejandro Vichot (Climate Dynamics, 2015)

Reassessing global change research priorities in mediterranean terrestrial ecosystems: how far have we come and where do we go from here? - E. Doblas‐Miranda; J. Martínez‐Vilalta; F. Lloret; A. Álvarez; A. Ávila; F. J. Bonet; L. Brotons; J. Castro; J. Curiel Yuste; M. Díaz; P. Ferrandis; E. García‐Hurtado; et al. (Global Ecology and Biogeography, 2015)
Aim Mediterranean terrestrial ecosystems serve as reference laboratories for the investigation of global change because of their transitional climate, the high spatiotemporal variability of their environmental conditions, a rich and unique biodiversity and a wide range of socio‐economic conditions. As scientific development and environmental pressures increase, it is increasingly necessary to evaluate recent progress and to challenge research priorities in the face of global change. Location Mediterranean terrestrial ecosystems. Methods This article revisits the research priorities proposed in a 1998 assessment. Results A new set of research priorities is proposed: (1) to establish the role of the landscape mosaic on fire‐spread; (2) to further research the combined effect of different drivers on pest expansion; (3) to address the interaction between drivers of global change and recent forest management practices; (4) to obtain more realistic information on the impacts of global change and ecosystem services; (5) to assess forest mortality events associated with climatic extremes; (6) to focus global change research on identifying and managing vulnerable areas; (7) to use the functional traits concept to study resilience after disturbance; (8) to study the relationship between genotypic and phenotypic diversity as a source of forest resilience; (9) to understand the balance between C storage and water resources; (10) to analyse the interplay between landscape‐scale processes and biodiversity conservation; (11) to refine models by including interactions between drivers and socio‐economic contexts; (12) to understand forest–atmosphere feedbacks; (13) to represent key mechanisms linking plant hydraulics with landscape hydrology. Main conclusions (1) The interactive nature of different global change drivers remains poorly understood. (2) There is a critical need for the rapid development of regional‐ and global‐scale models that are more tightly connected with large‐scale experiments, data networks and management practice. (3) More attention should be directed to drought‐related forest decline and the current relevance of historical land use.

Identifying oceanic foraging grounds of sea turtles in the Atlantic using lead isotopes - Melania C. López-Castro; Karen A. Bjorndal; George D. Kamenov; Alan B. Bolten (Marine Biology, 2014)

Reference genes for RT-qPCR studies in Corynebacterium pseudotuberculosis identified through analysis of RNA-seq data - Daiane M. Carvalho; Pablo H. de Sá; Thiago L. P. Castro; Rodrigo D. Carvalho; Anne Pinto; Danilo J. P. Gil; Priscilla Bagano; Bruno Bastos; Lilia F. M. Costa; Roberto Meyer; Artur Silva; Vasco Azevedo; et al. (Antonie van Leeuwenhoek, 2014)

Relative mRNA expression and immunolocalization for transforming growth factor-beta (TGF-β) and their effect on in vitro development of caprine preantral follicles - G. Q. Rodrigues; M. J. Bertoldo; I. R. Brito; C. M. G. Silva; A. D. Sales; S. V. Castro; N. Duffard; Y. Locatelli; P. Mermillod; C. H. Lobo; C. C. Campello; A. P. R. Rodrigues; et al. (In Vitro Cellular & Developmental Biology - Animal, 2014)

Allocation trade‐offs dominate the response of tropical forest growth to seasonal and interannual drought - Christopher E. Doughty; Yadvinder Malhi; Alejandro Araujo-Murakami; Daniel B. Metcalfe; Javier E. Silva-Espejo; Luzmila Arroyo; Juan P. Heredia; Erwin Pardo-Toledo; Luz M. Mendizabal; Victor D. Rojas-Landivar; Meison Vega-Martinez; Marcio Flores-Valencia; et al. (Ecology, 2014)
What determines the seasonal and interannual variation of growth rates in trees in a tropical forest? We explore this question with a novel four‐year high‐temporal‐resolution data set of carbon allocation from two forest plots in the Bolivian Amazon. The forests show strong seasonal variation in tree wood growth rates, which are largely explained by shifts in carbon allocation, and not by shifts in total productivity. At the deeper soil plot, there was a clear seasonal trade‐off between wood and canopy NPP, while the shallower soils plot showed a contrasting seasonal trade‐off between wood and fine roots. Although a strong 2010 drought reduced photosynthesis, NPP remained constant and increased in the six‐month period following the drought, which indicates usage of significant nonstructural carbohydrate stores. Following the drought, carbon allocation increased initially towards the canopy, and then in the following year, allocation increased towards fine‐root production. Had we only measured woody growth at these sites and inferred total NPP, we would have misinterpreted both the seasonal and interannual responses. In many tropical forest ecosystems, we propose that changing tree growth rates are more likely to reflect shifts in allocation rather than changes in overall productivity. Only a whole NPP allocation perspective can correctly interpret the relationship between changes in growth and changes in productivity.

Coyotes, deer, and wildflowers: diverse evidence points to a trophic cascade - Nickolas M. Waser; Mary V. Price; Daniel T. Blumstein; S. Reneé Arózqueta; Betsabé D. Castro Escobar; Richard Pickens; Alessandra Pistoia (The Science of Nature, 2014)

A genome-wide association study on copy-number variation identifies a 11q11 loss as a candidate susceptibility variant for colorectal cancer - C. Fernandez-Rozadilla; J. B. Cazier; I. Tomlinson; A. Brea-Fernández; M. J. Lamas; M. Baiget; L. A. López-Fernández; J. Clofent; L. Bujanda; D. Gonzalez; L. de Castro; K. Hemminki; et al. (Human Genetics, 2014)

Effect of water restriction on total phenolics and antioxidant properties of Amburana cearensis (Fr. Allem) A.C. Smith cotyledons during seed imbibition - Erica P. L. Pereira; Paulo R. Ribeiro; Marta B. Loureiro; Renato D. de Castro; Luzimar G. Fernandez (Acta Physiologiae Plantarum, 2014)

Myofibroblasts and the extracellular matrix network in post-myocardial infarction cardiac remodeling - Yonggang Ma; Lisandra E. de Castro Brás; Hiroe Toba; Rugmani Padmanabhan Iyer; Michael E. Hall; Michael D. Winniford; Richard A. Lange; Suresh C. Tyagi; Merry L. Lindsey (Pflügers Archiv - European Journal of Physiology, 2014)

Assessing the accuracy of mosaics from unmanned aerial vehicle (UAV) imagery for precision agriculture purposes in wheat - D. Gómez-Candón; A. I. De Castro; F. López-Granados (Precision Agriculture, 2014)

Basin‐scale phenology and effects of climate variability on global timing of initial seaward migration of Atlantic salmon ( Salmo salar ) - Jaime Otero; Jan Henning L'Abée‐Lund; Ted Castro‐Santos; Kjell Leonardsson; Geir O. Storvik; Bror Jonsson; Brian Dempson; Ian C. Russell; Arne J. Jensen; Jean‐Luc Baglinière; Mélanie Dionne; John D. Armstrong; et al. (Global Change Biology, 2014)
Migrations between different habitats are key events in the lives of many organisms. Such movements involve annually recurring travel over long distances usually triggered by seasonal changes in the environment. Often, the migration is associated with travel to or from reproduction areas to regions of growth. Young anadromous Atlantic salmon ( Salmo salar ) emigrate from freshwater nursery areas during spring and early summer to feed and grow in the North Atlantic Ocean. The transition from the freshwater (‘parr’) stage to the migratory stage where they descend streams and enter salt water (‘smolt’) is characterized by morphological, physiological and behavioural changes where the timing of this parr‐smolt transition is cued by photoperiod and water temperature. Environmental conditions in the freshwater habitat control the downstream migration and contribute to within‐ and among‐river variation in migratory timing. Moreover, the timing of the freshwater emigration has likely evolved to meet environmental conditions in the ocean as these affect growth and survival of the post‐smolts. Using generalized additive mixed‐effects modelling, we analysed spatio‐temporal variations in the dates of downstream smolt migration in 67 rivers throughout the North Atlantic during the last five decades and found that migrations were earlier in populations in the east than the west. After accounting for this spatial effect, the initiation of the downstream migration among rivers was positively associated with freshwater temperatures, up to about 10 °C and levelling off at higher values, and with sea‐surface temperatures. Earlier migration occurred when river discharge levels were low but increasing. On average, the initiation of the smolt seaward migration has occurred 2.5 days earlier per decade throughout the basin of the North Atlantic. This shift in phenology matches changes in air, river, and ocean temperatures, suggesting that Atlantic salmon emigration is responding to the current global climate changes.

Comparative transcriptional analysis reveals differential gene expression between Sand Daffodil tissues - Bruna De Felice; Francesco Manfellotto; Raffaella D’Alessandro; Olga De Castro; Antonietta Di Maio; Marco Trifuoggi (Genetica, 2013)

Generating anatomical models of the heart and the aorta from medical images for personalized physiological simulations - J. Weese; A. Groth; H. Nickisch; H. Barschdorf; F. M. Weber; J. Velut; M. Castro; C. Toumoulin; J. L. Coatrieux; M. De Craene; G. Piella; C. Tobón-Gomez; et al. (Medical & Biological Engineering & Computing, 2013)

Evaluation of an ensemble of regional climate model simulations over South America driven by the ERA-Interim reanalysis: model performance and uncertainties - Silvina A. Solman; E. Sanchez; P. Samuelsson; R. P. da Rocha; L. Li; J. Marengo; N. L. Pessacg; A. R. C. Remedio; S. C. Chou; H. Berbery; H. Le Treut; M. de Castro; et al. (Climate Dynamics, 2013)

Future sea ice conditions in Western H udson B ay and consequences for polar bears in the 21st century - Laura Castro de la Guardia; Andrew E. Derocher; Paul G. Myers; Arjen D. Terwisscha van Scheltinga; Nick J. Lunn (Global Change Biology, 2013)
The primary habitat of polar bears is sea ice, but in Western H udson B ay ( WH ), the seasonal ice cycle forces polar bears ashore each summer. Survival of bears on land in WH is correlated with breakup and the ice‐free season length, and studies suggest that exceeding thresholds in these variables will lead to large declines in the WH population. To estimate when anthropogenic warming may have progressed sufficiently to threaten the persistence of polar bears in WH , we predict changes in the ice cycle and the sea ice concentration ( SIC ) in spring (the primary feeding period of polar bears) with a high‐resolution sea ice‐ocean model and warming forced with 21st century IPCC greenhouse gas ( GHG ) emission scenarios: B1 (low), A1B (medium), and A2 (high). We define critical years for polar bears based on proposed thresholds in breakup and ice‐free season and we assess when ice‐cycle conditions cross these thresholds. In the three scenarios, critical years occur more commonly after 2050. From 2001 to 2050, 2 critical years occur under B1 and A2, and 4 under A1B; from 2051 to 2100, 8 critical years occur under B1, 35 under A1B and 41 under A2. Spring SIC in WH is high (>90%) in all three scenarios between 2001 and 2050, but declines rapidly after 2050 in A1B and A2. From 2090 to 2100, the mean spring SIC is 84 (±7)% in B1, 56 (±26)% in A1B and 20 (±13)% in A2. Our predictions suggest that the habitat of polar bears in WH will deteriorate in the 21st century. Ice predictions in A1B and A2 suggest that the polar bear population may struggle to persist after ca. 2050. Predictions under B1 suggest that reducing GHG emissions could allow polar bears to persist in WH throughout the 21st century.

Control of the European rabbit in central Spain - Carlos Antonio Ríos-Saldaña; Miguel Delibes-Mateos; Francisca Castro; Emilia Martínez; Juan Mario Vargas; Brian D. Cooke; Rafael Villafuerte (European Journal of Wildlife Research, 2013)

Folate metabolite profiling of different cell types and embryos suggests variation in folate one-carbon metabolism, including developmental changes in human embryonic brain - Kit-Yi Leung; Sandra C. P. De Castro; Filipe Cabreiro; Peter Gustavsson; Andrew J. Copp; Nicholas D. E. Greene (Molecular and Cellular Biochemistry, 2013)

PAH air pollution at a Portuguese urban area: carcinogenic risks and sources identification - K. Slezakova; J. C. M. Pires; D. Castro; M. C. M. Alvim-Ferraz; C. Delerue-Matos; S. Morais; M. C. Pereira (Environmental Science and Pollution Research, 2013)

Transmission of lymphocystis disease virus to cultured gilthead seabream, S parus aurata L ., larvae - I Cano; E J Valverde; E Garcia‐Rosado; M C Alonso; B Lopez‐Jimena; J B Ortiz‐Delgado; J J Borrego; C Sarasquete; D Castro (Journal of Fish Diseases, 2013)
The transmission of lymphocystis disease virus ( LCDV ) to gilthead seabream, S parus aurata L ., larvae was investigated using fertilized eggs from a farm with previous reports of lymphocystis disease. LCDV genome was detected by PCR ‐hybridization in blood samples from 17.5% of the asymptomatic gilthead seabream broodstock analysed. Using the same methodology, eggs spawned from these animals were LCDV positive, as well as larvae hatched from them. The presence of infective viral particles was confirmed by cytopathic effects development on SAF ‐1 cells. Whole‐mount in situ hybridization ( ISH ) and immunohistochemistry ( IHC ) showed the presence of LCDV in the epidermis of larvae hatched from LCDV ‐positive eggs. When fertilized eggs were disinfected with iodine, no viral DNA was detected either in eggs (analysed by PCR ‐hybridization) or in larvae ( PCR ‐hybridization and ISH ). These results suggest the vertical transmission of LCDV , the virus being transmitted on the egg surface. Larvae hatched from disinfected eggs remain LCDV negative during the endotrophic phase, as showed by PCR ‐hybridization, ISH and IHC . After feeding on LCDV ‐positive rotifers, viral antigens were observed in the digestive tract, which suggests that viral entry could be achieved via the alimentary canal, and that rotifers can act as a vector in LCDV transmission to gilthead seabream larvae.

Mapping wild pear trees ( Pyrus bourgaeana ) in Mediterranean forest using high-resolution QuickBird satellite imagery - S. Arenas-Castro; Y. Julien; J.C. Jiménez-Muñoz; J.A. Sobrino; J. Fernández-Haeger; D. Jordano-Barbudo (International Journal of Remote Sensing, 2013)

Western Mediterranean precipitation over the last 300 years from instrumental observations - D. Camuffo; C. Bertolin; N. Diodato; C. Cocheo; M. Barriendos; F. Dominguez-Castro; E. Garnier; M. J. Alcoforado; M. F. Nunes (Climatic Change, 2013)

Bacterioplankton community composition in Portuguese water bodies under a severe summer drought - D. Figueiredo; B. Castro; M. Pereira; A. Correia (Community Ecology, 2012)

Performance of a multi-RCM ensemble for South Eastern South America - A. F. Carril; C. G. Menéndez; A. R. C. Remedio; F. Robledo; A. Sörensson; B. Tencer; J.-P. Boulanger; M. de Castro; D. Jacob; H. Le Treut; L. Z. X. Li; O. Penalba; et al. (Climate Dynamics, 2012)

Mapping resistance genes conferring tolerance to RWA (Diuraphis noxia) in barley (Hordeum vulgare) - E. Tocho; M. Ricci; M. S. Tacaliti; D. O. Giménez; A. Acevedo; U. Lohwasser; A. Börner; A. M. Castro (Euphytica, 2012)

Tuberculosis: Finding a New Potential Antimycobacterium Derivative in a Aldehyde–Arylhydrazone–Oxoquinoline Series - Fernanda C. Santos; Helena C. Castro; Maria Cristina S. Lourenço; Paula A. Abreu; Pedro N. Batalha; Anna C. Cunha; Guilherme S. L. Carvalho; Carlos R. Rodrigues; Cid A. Medeiros; Simone D. Souza; Vitor F. Ferreira; Maria C. B. V. Souza (Current Microbiology, 2012)

Experimental transmission of the mild strain of Tomato yellow leaf curl virus (TYLCV) to Amaranthus dubius by Bemisia tabaci - P. Güerere; D. T. Chirinos; F. Geraud-Pouey; E. Moriones; M. A. Santana; M. A. Franco; I. Galindo-Castro; G. Romay (Phytoparasitica, 2012)

Further Studies on the Hypothesis of PARP-1 Inhibition as a Strategy for Lessening the Long-Term Effects Produced by Perinatal Asphyxia: Effects of Nicotinamide and Theophylline on PARP-1 Activity in Brain and Peripheral Tissue - C. Allende-Castro; P. Espina-Marchant; D. Bustamante; E. Rojas-Mancilla; T. Neira; M. A. Gutierrez-Hernandez; D. Esmar; J. L. Valdes; P. Morales; P. J. Gebicke-Haerter; M. Herrera-Marschitz (Neurotoxicity Research, 2012)

Muscular strength and markers of insulin resistance in European adolescents: the HELENA Study - D. Jiménez-Pavón; F. B. Ortega; J. Valtueña; J. Castro-Piñero; S. Gómez-Martínez; M. Zaccaria; F. Gottrand; D. Molnár; M. Sjöström; M. González-Gross; M. J. Castillo; L. A. Moreno; et al. (European Journal of Applied Physiology, 2012)

Development of a Design Space for a Unit Operation: Illustration Using Compression-Mix Blending Process for the Manufacture of a Tablet Dosage Form - Shiva G. Kapsi; Lan D. Castro; Fran X. Muller; Thomas J. Wrzosek (Journal of Pharmaceutical Innovation, 2012)

Sea surface temperature anomalies, seasonal cycle and trend regimes in the Eastern Pacific coast - A. Ramos-Rodríguez; D. B. Lluch-Cota; S. E. Lluch-Cota; A. Trasviña-Castro (Ocean Science, 2012)
We used the extended reconstruction of sea surface temperature (ERSST) to analyze the variation of surface temperature and the seasonal cycle along the coast of the eastern Pacific (60° N–60° S, 61 pixels alongshore) from 1950 to 2010 (732 months). First, we analyzed the monthly anomalies and looked for a relationship of such anomalies with total solar irradiance (TSI) and then the Regime Shift Detector (RSD) was applied to detect possible temperature regimes in the series. Afterwards, we calculated a yearly temperature range per pixel (amplitude of seasonal cycle) and through the subtraction of a latitudinal theoretical curve of temperature based on solar irradiance, the residuals of the seasonal cycle were obtained. The results showed an almost complete spatial synchrony and dominance of negative anomalies from 1950 to mid-late 1970's, with a switch to near-zero and positive anomalies that lasted up to late 1990's when a new shift to negative values was detected. Such a shift lasted until the early 2000's when positive anomalies appeared again but there was a change to negative anomalies in the late 2000's. These results were supported by the RSD. The TSI variability shows a clear relationship with that of sea surface temperature anomalies and with the regime changes. This is probably due to a difference in the amount of energy received from the sun. Comparing the "cool regime" versus the "warm regime", the second one received 0.39% more energy (approximately 3 × 108 J m−2) from the sun. Seasonal cycles show larger ranges at northern latitudes (>40° N), northern tropical-temperate transition zone (20°–26° N) and in the tropical-equatorial band (0°–30° S). The smallest ranges occur at 0°–16° N and 50°–60° S. The residuals (seasonal minus the theoretical curve) indicated a clear modulation due to advection by ocean currents.

Ecological drivers of group living in two populations of the communally rearing rodent, Octodon degus - Luis A. Ebensperger; Raúl Sobrero; Verónica Quirici; Rodrigo A. Castro; Liliana Ortiz Tolhuysen; Francisco Vargas; Joseph Robert Burger; René Quispe; Camila P. Villavicencio; Rodrigo A. Vásquez; Loren D. Hayes (Behavioral Ecology and Sociobiology, 2012)

Variability of the monthly European temperature and its association with the Atlantic sea‐surface temperature from interannual to multidecadal scales - S. R. Gámiz‐Fortis; M. J. Esteban‐Parra; D. Pozo‐Vázquez; Y. Castro‐Díez (International Journal of Climatology, 2011)
The relationships between the main patterns of variability of the Atlantic sea‐surface temperatures (SSTs) and the European land‐surface temperatures (LSTs) at interannual‐to‐multidecadal time scales are investigated along the period 1872–2004. Principal component analysis (PCA) is used firstly to obtain the main spatio‐temporal patterns of variability of the LSTs and SSTs. Singular Spectral Analysis (SSA) is then used to decompose the time series associated with these patterns into nonlinear trends and quasi‐periodic oscillations, searching for common oscillatory modes to the SSTs and LSTs. The potential predictability of the LSTs based on the SSTs is also analysed. Regarding the SSA results, three robust oscillations of periods around 13.7, 7.5 and 5.2 years, present both in the Atlantic SSTs and north‐western European LSTs, were isolated. These oscillations were found to be associated mainly with a quadripolar SST pattern in the North Atlantic region, usually related to the North Atlantic Oscillation (NAO) atmospheric mode of variability. The predictability study revealed that the SSTs of the Atlantic Ocean are able to account for about 12% of the north‐western European LSTs variance. Additionally, an oscillatory component with period around 3.6 years was identified, but no significant connection between SST and LST was found for this mode. In addition, at this time scale, we find that the El Niño‐Southern Oscillation (ENSO) is leading the Atlantic SST quadripolar pattern by 6 months. Finally, the analysis of the nonlinear trends showed the presence of oscillations with periods around 60–100 years, both in the SSTs and LSTs. At these later time scales, our results reveal that the multidecadal behaviour of the southern European LSTs is related to Atlantic Multidecadal Oscillation (AMO) during the period 1872–1940, unlike the northern and eastern European LSTs, while, during the period 1941–2004, the AMO sign seems to be present in whole Europe. Copyright © 2010 Royal Meteorological Society

Microsatellites reveal widespread predominance of an invasive over an indigenous Bemisia tabaci in Venezuela - G. Romay; F. Geraud-Pouey; D. T. Chirinos; M. A. Santana; I. Galindo-Castro; L. M. Márquez (Phytoparasitica, 2011)

Soluble Fas and Fas ligand in HIV/HCV coinfected patients and impact of HCV therapy - M. Guzmán-Fulgencio; J. Berenguer; M. García-Álvarez; D. Micheloud; J. C. López; J. Cosín; I. Fernández de Castro; P. Catalán; P. Miralles; S. Resino (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Enhancing Oncology Health Care Provider's Sensitivity to Cultural Communication to Reduce Cancer Disparities: A Pilot Study - Gwendolyn P. Quinn; Julio Jimenez; Cathy D. Meade; Teresita Muñoz-Antonia; Clement K. Gwede; Eida Castro; Susan T. Vadaparampil; Vani Nath Simmons; Jessica McIntyre; Theresa T. Crocker; Thomas H. Brandon (Journal of Cancer Education, 2011)

Identification of a novel prostate cancer susceptibility variant in the KLK3 gene transcript - Z. Kote-Jarai; A. Amin Al Olama; D. Leongamornlert; M. Tymrakiewicz; E. Saunders; M. Guy; G. G. Giles; G. Severi; M. Southey; J. L. Hopper; K. C. Sit; J. M. Harris; et al. (Human Genetics, 2011)

Morphological, morphometric, meristic and osteological evidence for two species of hake (Actinopterygii: Gadiformes: Merluccius ) in Argentinean waters - J. M. Díaz de Astarloa; S. I. Bezzi; M. González Castro; E. Mabragaña; D. Hernández; S. M. Delpiani; D. E. Figueroa; M. B. Cousseau; M. Y. Deli Antoni; L. Tringali (Journal of Fish Biology, 2011)
Morphologically, both classic and landmark‐based morphometry and meristic analyses of 241 specimens of Merluccius , along with the re‐examination of six paratype specimens of Merluccius hubbsi , the holotype and three paratypes of Merluccius patagonicus and the syntype of Merluccius australis revealed the presence of only two species of Merluccius in Argentinean waters. Internal structures (hyomandibula, urohyal and sagitta otolith) of M. hubbsi were compared to those reported for M. patagonicus and were shown to have identical morphology. Type specimens of M. patagonicus showed a complete overlap in morphometric and meristic characters with M. hubbsi , whereas M. australis had a greater number of second dorsal and anal‐fin rays, and more lateral‐line scales. In addition, M. australis had a smaller eye and longer snout than M. hubbsi and M. patagonicus . The results indicate that there is no evidence for a third hake species in Argentinean waters. Merluccius patagonicus is a synonym of M. hubbsi .

Synthesis, characterization, and application of modified silica in the removal and preconcentration of lead ions from natural river water - Guilherme Ferreira; Laercio Caetano; Renata S. D. Castro; Pedro Magalhães Padilha; Gustavo Rocha Castro (Clean Technologies and Environmental Policy, 2011)

A generalized calibration procedure for in vivo transit dosimetry using siemens electronic portal imaging devices - Andrea Fidanzio; Francesca Greco; Laura Gargiulo; Savino Cilla; Domenico Sabatino; Massimo Cappiello; Cinzia Di Felice; Elisabetta Di Castro; Luigi Azario; Mariateresa Russo; Luciano Pompei; Guido D’Onofrio; et al. (Medical & Biological Engineering & Computing, 2011)

Improved Albendazole Dissolution Rate in Pluronic 188 Solid Dispersions - Silvina G. Castro; Sergio Sanchez Bruni; Carlos E. Lanusse; Daniel A. Allemandi; Santiago D. Palma (AAPS PharmSciTech, 2010)

Establishing a serological surveillance protocol for rabbit hemorrhagic disease by combining mathematical models and field data: implication for rabbit conservation - Irene Cotilla; Miguel Delibes-Mateos; Esther Ramírez; Francisca Castro; Brian D. Cooke; Rafael Villafuerte (European Journal of Wildlife Research, 2010)

A new genotype of Lymphocystivirus isolated from cultured gilthead seabream, Sparus aurata L., and Senegalese sole, Solea senegalensis (Kaup) - I Cano; E J Valverde; B Lopez‐Jimena; M C Alonso; E Garcia‐Rosado; C Sarasquete; J J Borrego; D Castro (Journal of Fish Diseases, 2010)

Selection of ecological indicators for the conservation, management and monitoring of Mediterranean coastal salinas - Enrique López; Pedro A. Aguilera; María F. Schmitz; Hermelindo Castro; Francisco D. Pineda (Environmental Monitoring and Assessment, 2010)

Haplotype analyses, mechanism and evolution of common double mutants in the human LDL receptor gene - M. T. Tejedor; A. Cenarro; D. Tejedor; M. Stef; R. Mateo-Gallego; I. de Castro; A. L. García-Otin; L. V. Monteagudo; F. Civeira; M. Pocovi (Molecular Genetics and Genomics, 2010)

Species identification using a small nuclear gene fragment: application to sympatric wild carnivores from South-western Europe - R. Oliveira; D. Castro; R. Godinho; G. Luikart; P. C. Alves (Conservation Genetics, 2010)

Antioxidant system activation by mercury in Pfaffia glomerata plantlets - N. S. Calgaroto; G. Y. Castro; D. Cargnelutti; L. B. Pereira; J. F. Gonçalves; L. V. Rossato; F. G. Antes; V. L. Dressler; E. M. M. Flores; M. R. C. Schetinger; F. T. Nicoloso (BioMetals, 2010)

Detection of infectious pancreatic necrosis virus (IPNV) from asymptomatic redbanded seabream, Pagrus auriga Valenciennes, and common seabream, Pagrus pagrus (L.), using a non‐destructive procedure - B Lopez‐Jimena; E Garcia‐Rosado; C Infante; I Cano; M Manchado; D Castro; J J Borrego; M C Alonso (Journal of Fish Diseases, 2010)
A non‐destructive procedure based on nested RT‐PCR and dot‐blot hybridization has been developed for the detection of asymptomatic IPNV‐carrier fish. The pair of primers designed for RT‐PCR amplified a 599‐bp fragment of the pVP2 region within the polyprotein gene, resulting in the detection of IPNV genotype III.1. The use of a nested RT‐PCR allowed the amplification of IPNV genotypes III.1 and I.2. In addition, a 191‐bp probe was designed for hybridization studies used in combination with the nested RT‐PCR. The application of the nested RT‐PCR to analyse blood samples from asymptomatic redbanded seabream, Pagrus auriga , and common seabream, P. pagrus , specimens showed a 53.1% and 77.8% prevalence of IPNV‐carriers, respectively. The combination of nested RT‐PCR and dot‐blot hybridization increased the detection rates up to 100% for redbanded seabream and 94.4% for common seabream. Therefore, the protocol described in this study is highly sensitive and specific for the detection of IPNV in asymptomatic carrier fish, and, in addition, the results demonstrate the carrier state in two newly cultured sparid species in southern Spain.

Downscaling extreme month-long anomalies in southern South America - C. G. Menéndez; M. de Castro; J.-P. Boulanger; A. D’Onofrio; E. Sanchez; A. A. Sörensson; J. Blazquez; A. Elizalde; D. Jacob; H. Le Treut; Z. X. Li; M. N. Núñez; et al. (Climatic Change, 2010)

Frequency distribution of XbaIG > T and HaeIIIT > C GLUT1 polymorphisms among different Brazilian ethnic groups - G. C. S. Costa; L. C. J. Alcantara; R. Azevedo; G. Muricy; S. H. Kashima; D. T. Covas; B. Galvão-Castro; S. R. Gadelha (Molecular Biology Reports, 2010)

Polychlorinated Biphenyls and Biotransformation Enzymes in Three Species of Sea Turtles from the Baja California Peninsula of Mexico - K. L. Richardson; M. Lopez Castro; S. C. Gardner; D. Schlenk (Archives of Environmental Contamination and Toxicology, 2010)

Relationship between geomorphology and contamination with weathered hydrocarbons in an old river levee/marsh association - R. H. Adams; D. Olán-Castro; F. J. Guzmán-Osorio; I. J. Diaz-Ramírez (International Journal of Environmental Science and Technology, 2009)

Trophic ecology of the Southern Grey Shrike (Lanius meridionalis) in insular environments: the influence of altitude and seasonality - D. P. Padilla; A. González-Castro; C. Nieves; M. Nogales (Journal of Ornithology, 2009)

Application of in situ detection techniques to determine the systemic condition of lymphocystis disease virus infection in cultured gilt‐head seabream, Sparus aurata L. - I Cano; P Ferro; M C Alonso; C Sarasquete; E Garcia‐Rosado; J J Borrego; D Castro (Journal of Fish Diseases, 2009)
Immunohistochemistry (IHC) and in situ hybridization (ISH) techniques have been used for the detection of lymphocystis disease virus (LCDV) in formalin‐fixed, paraffin‐embedded tissues from gilt‐head seabream, Sparus aurata L. Diseased and recovered fish from the same population were analysed. IHC was performed with a polyclonal antibody against a 60‐kDa viral protein. A specific digoxigenin‐labelled probe, obtained by PCR amplification of a 270‐bp fragment of the gene coding the LCDV major capsid protein, was used for ISH. LCDV was detected in skin dermis and gill lamellae, as well as in several internal organs such as the intestine, liver, spleen and kidney using both techniques. Fibroblasts, hepatocytes and macrophages seem to be target cells for virus replication. The presence of lymphocystis cells in the dermis of the skin and caudal fin, and necrotic changes in the epithelium of proximal renal tubules were the only histological alterations observed in fish showing signs of the disease.

The occurrence of Mt Barca flank eruption in the evolution of the NW periphery of Etna volcano (Italy) - S. Branca; P. Del Carlo; M. D. Lo Castro; E. De Beni; J. Wijbrans (Bulletin of Volcanology, 2009)

Mapping quantitative trait loci for growth responses to exogenously applied stress induced hormones in wheat - A. M. Castro; M. S. Tacaliti; D. Giménez; E. Tocho; O. Dobrovolskaya; A. Vasicek; M. Collado; J. W. Snape; A. Börner (Euphytica, 2008)

Identification of a Potential Lead Structure for Designing New Antimicrobials to Treat Infections Caused by Staphylococcus epidermidis-Resistant Strains - Luiz C. S. Pinheiro; Paula A. Abreu; Ilidio F. Afonso; Bruno Leal; Luiz C. D. Corrêa; Júlio C. Borges; Isakelly P. Marques; André L. Lourenço; Plinio Sathler; Andre L. dos Santos; Cid A. Medeiros; Lúcio M. Cabral; et al. (Current Microbiology, 2008)

Flow cytometric and cytogenetic analyses of Iberian Peninsula Festuca spp. - J. Loureiro; D. Kopecký; S. Castro; C. Santos; P. Silveira (Plant Systematics and Evolution, 2007)

Metal Content of the Gulf of California Blue Shrimp Litopenaeus stylirostris (Stimpson) - M. G. Frías-Espericueta; G. Izaguirre-Fierro; F. Valenzuela-Quiñonez; J. I. Osuna-López; D. Voltolina; G. López-López; M. D. Muy-Rangel; W. Rubio-Castro (Bulletin of Environmental Contamination and Toxicology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

An intercomparison of regional climate simulations for Europe: assessing uncertainties in model projections - M. Déqué; D. P. Rowell; D. Lüthi; F. Giorgi; J. H. Christensen; B. Rockel; D. Jacob; E. Kjellström; M. de Castro; B. van den Hurk (Climatic Change, 2007)

Interspecific differentiation and intraspecific substructure in two closely related clupeids with extensive hybridization, Alosa alosa and Alosa fallax - P. Alexandrino; R. Faria; D. Linhares; F. Castro; M. Le Corre; R. Sabatié; J. L. Baglinière; S. Weiss (Journal of Fish Biology, 2006)
In this study, the evolutionary relationships within and among populations of European shads, Alosa alosa and Alosa fallax , was investigated. Screening of allelic variation across eight allozyme loci and sequencing 448 bp of the mtDNA cytochrome b gene in 14 rivers throughout the range of the species supported that the two taxa were independent lineages (1·3% net nucleotide divergence) despite extensive hybridization. Genetic diversity and structure was considerably higher in A. fallax than A. alosa and the former species revealed evidence of distinct lineages in the Mediterranean and Atlantic basins. A Bayesian clustering approach combined with gill raker counts verified that individuals of the two species could be assigned to their parent group with relatively high confidence. Evaluation of hybridization in the Lima and Mondego Rivers in Portugal provided evidence that introgression is extensive but is not currently obscuring (through hybrid swarming) the diagnosability of the two species.

Sensitivity studies of the RegCM3 simulation of summer precipitation, temperature and local wind field in the Caribbean Region - D. Martínez-Castro; R. Porfirio da Rocha; A. Bezanilla-Morlot; L. Alvarez-Escudero; J. P. Reyes-Fernández; Y. Silva-Vidal; R. W. Arritt (Theoretical and Applied Climatology, 2006)

Coat protein gene sequence of a Mexican isolate of Sugarcane mosaic virus and its infectivity in maize and sugarcane plants - F. Espejel; D. Jeffers; J. C. Noa-Carrazana; S. Ruiz-Castro; L. Silva-Rosales (Archives of Virology, 2006)

Apoptotic effect of fludarabine is independent of expression of IAPs in B-cell chronic lymphocytic leukemia - K. L. Silva; D. V. Vasconcellos; E. D. de Paula Castro; A. M. Coelho; R. Linden; R. C. Maia (Apoptosis, 2006)

Population stratification confounds genetic association studies among Latinos - Shweta Choudhry; Natasha E. Coyle; Hua Tang; Keyan Salari; Denise Lind; Suzanne L. Clark; Hui-Ju Tsai; Mariam Naqvi; Angie Phong; Ngim Ung; Henry Matallana; Pedro C. Avila; et al. (Human Genetics, 2006)

Geotechnical Site Characterisation in the Umbria-Marche Area and Evaluation of Earthquake Site-Response - L. Luzi; D. Bindi; G. Franceschina; F. Pacor; R. R. Castro (Pure and Applied Geophysics, 2005)

Geochemical evolution of groundwater in the Maneadero coastal aquifer during a dry year in Baja California, Mexico - L. Walter Daesslé; Edith C. Sánchez; Victor F. Camacho-Ibar; Leopoldo G. Mendoza-Espinosa; José D. Carriquiry; Victor A. Macias; Pedro G. Castro (Hydrogeology Journal, 2005)

Structural study of synthetic mica–montmorillonite by means of 2D MAS NMR experiments - M. D. Alba; M. A. Castro; P. Chain; M. Naranjo; A. C. Perdigón (Physics and Chemistry of Minerals, 2005)

Isolation of lymphocystis disease virus from sole, Solea senegalensis Kaup, and blackspot sea bream, Pagellus bogaraveo (Brünnich) - M C Alonso; I Cano; E Garcia‐Rosado; D Castro; J Lamas; J L Barja; J J Borrego (Journal of Fish Diseases, 2005)
Two viruses were isolated from cultured sole, Solea senegalensis , and wild blackspot sea bream, Pagellus bogaraveo , and preliminarily characterized as lymphocystis disease viruses (LCDVs). Viral isolates were characterized by morphological, biochemical and biophysical properties. In addition, the susceptibility of four fish cell lines was also tested. LCDV isolates developed cytopathic effects on the SAF‐1 cell line at 5 and 6 days post‐infection and reached titres of 10 6 TCID 50 mL −1 . The antigenic and structural protein analysis of the two new LCDV isolates showed identical profiles to that obtained for LCDV strain Leetown NFH (ATCC VR‐342), used as a reference viral strain, and for an LCDV isolate collected from gilt‐head sea bream, Sparus aurata , cultured in southern Spain. Molecular confirmation was performed by polymerase chain reaction. Specific primers for LCDV produced a 270‐bp DNA fragment, the expected size for LCDV.

Plant species richness and spatial organization at different small scales in western Mediterranean landscapes - J. M. De. Miguel; L. Ramírez-Sanz; I. Castro; M. Costa-Tenorio; M. A. Casado; F. D. Pineda (Plant Ecology, 2005)

Construction and characterization of a plant transformation-competent BIBAC library of the black Sigatoka-resistant banana Musa acuminata cv. Tuu Gia (AA) - E. Ortiz-Vázquez; D. Kaemmer; H-B. Zhang; J. Muth; M. Rodríguez-Mendiola; C. Arias-Castro; Andrew James (Theoretical and Applied Genetics, 2005)

Limited nucleotide divergence over large spatial scales in the asterinid sea star Patiriella exigua - D. J. Colgan; M. Byrne; E. Rickard; L. R. Castro (Marine Biology, 2005)

Oxidation of ethanol to acetaldehyde and free radicals by rat testicular microsomes - Leandro N. Quintans; Gerardo D. Castro; Jos A. Castro (Archives of Toxicology, 2005)

El Niño–southern oscillation events and associated European winter precipitation anomalies - D. Pozo‐Vázquez; S. R. Gámiz‐Fortis; J. Tovar‐Pescador; M. J. Esteban‐Parra; Y. Castro‐Díez (International Journal of Climatology, 2005)
The winter precipitation anomalies in the European area have been analysed over the period 1900–98 based on the El Niño–Southern oscillation (ENSO) state. A set of winter and autumn ENSO events is first selected using the Sea‐Surface temperature (SST) data of the Niño 3 region, with the constraint that the ENSO event is well developed during the winter and autumn of study, and that it is an extreme event. Cold and warm ENSO events and periods that can be regarded as normal are selected. For the selected winter ENSO events and for the winter following the selected autumn ENSO events, composites of European winter precipitation anomalies have been obtained and compared with each other. A study of the consistency among events of the relationship between ENSO and precipitation anomalies was also carried out. The analysis of the winter precipitation anomalies based on the selected winter ENSO events shows the existence, for the European area and during La Niña events, of a statistically significant precipitation anomaly pattern with positive precipitation anomalies north of the British Isles and in the Scandinavian area and negative anomalies in southern Europe, resembling the precipitation pattern associated with the positive phase of the North Atlantic oscillation (NAO). Particularly, for the southwestern area of the Iberian Peninsula, the negative anomaly reaches 20% of the winter average precipitation. The consistency analysis shows that this precipitation pattern is not the result of a few major events, but rather that it is stable and qualitatively similar to that found during the positive phase of the NAO. A non‐linear response to ENSO is found in the eastern Mediterranean area: negative precipitation anomalies are found, having similar amplitude anomalies, both during El Niño and La Niña events. The analysis of the precipitation anomalies for the winter following the selected autumn ENSO events shows very similar results to those found for the previous analysis, thus suggesting the existence of a potential source of seasonal forecasting of European precipitation. An analysis of the sensitivity of the precipitation anomalies to the strength of the ENSO events shows that, when the strength of the ENSO increases, the magnitude of the rainfall anomalies does not change, but the area influenced and the coherence between events do increase slightly. Copyright © 2005 Royal Meteorological Society

Structural localization of Al 3+ ions in aluminosilicates: application of heteronuclear chemical shift correlation to 2:1 phyllosilicates - M. D. Alba; M. A. Castro; M. Naranjo; A. C. Perdign (Physics and Chemistry of Minerals, 2004)

Nramp1 deletion does not confer susceptibility to Rhodococcus equi infection in mice - Philippe Gros; Lucero Del Castro; Dianna Meyer; Ronald J. Martens; Noah D. Cohen; Jessica Harrington (Immunogenetics, 2004)

Herbaceous plant richness and vegetation cover in Mediterranean grasslands and shrublands - Miguel A. Casado; Isabel Castro; Lucía Ramírez-Sanz; Margarita Costa-Tenorio; Jose M. de Miguel; Francisco D. Pineda (Plant Ecology, 2004)

On the Composition of Airborne Particles Influenced by Emissions of the Volcano Popocatépetl in Mexico - J. C. Jiménez; G. B. Raga; D. Baumgardner; T. Castro; I. Rosas; A. Báez; O. Morton (Natural Hazards, 2004)

Assessment of regional seasonal rainfall predictability using the CPTEC/COLA atmospheric GCM - J. A. Marengo; I. F. A. Cavalcanti; P. Satyamurty; I. Trosnikov; C. A. Nobre; J. P. Bonatti; H. Camargo; G. Sampaio; M. B. Sanches; A. O. Manzi; C. A. C. Castro; C. D'Almeida; et al. (Climate Dynamics, 2003)

Mapping and pyramiding of qualitative and quantitative resistance to stripe rust in barley - A. J. Castro; F. Capettini; A. E. Corey; T. Filichkina; P. M. Hayes; A. Kleinhofs; D. Kudrna; K. Richardson; S. Sandoval-Islas; C. Rossi; H. Vivar (Theoretical and Applied Genetics, 2003)

Frequent Mitochondrial Gene Rearrangements at the Hymenopteran nad3-nad5 Junction - Mark Dowton; Lyda R. Castro; Sarah L. Campbell; Sharmilla D. Bargon; Andrew D. Austin (Journal of Molecular Evolution, 2003)

Molecular epidemiology of hepatitis B virus in Afro-Venezuelan populations - A. Quintero; D. Martínez; B. Alarcón de Noya; A. Costagliola; L. Urbina; N. González; F. Liprandi; D. Castro de Guerra; F. H. Pujol (Archives of Virology, 2002)

Numerical Analysis of Space–Time Finite Element Formulations for Miscible Displacements - Rigoberto G. Sanabria Castro; Sandra M. C. Malta; Abimael F. D. Loula; Luiz Landau (Computational Geosciences, 2001)

The Basques according to polymorphic Alu insertions - M. de Pancorbo; López-Martínez M.; Martínez-Bouzas C.; Castro A.; Fernández-Fernández I.; G. Antúnez de Mayolo; A. Antúnez de Mayolo; P. Antúnez de Mayolo; Rowold D.; Herrera R. (Human Genetics, 2001)

A study of NAO variability and its possible non-linear influences on European surface temperature - D. Pozo-Vázquez; M. J. Esteban-Parra; F. S. Rodrigo; Y. Castro-Díez (Climate Dynamics, 2001)

Identification of wheat chromosomes involved with different types of resistance against greenbug (Schizaphis graminum, Rond.) and the Russian wheat aphid (Diuraphis noxia, Mordvilko) - A.M. Castro; S. Ramos; A. Vasicek; A. Worland; D. Giménez; A.A. Clúa; E. Suárez (Euphytica, 2001)

An analysis of the variability of the North Atlantic Oscillation in the time and the frequency domains - D. Pozo-Vzquez; M.J. Esteban-Parra; F.S. Rodrigo; Y. Castro-Dez (International Journal of Climatology, 2000)

An analysis of the variability of the North Atlantic Oscillation in the time and the frequency domains - D. Pozo‐Vázquez; M.J. Esteban‐Parra; F.S. Rodrigo; Y. Castro‐Díez (International Journal of Climatology, 2000)

Rainfall variability in southern Spain on decadal to centennial time scales - F.S. Rodrigo; M.J. Esteban-Parra; D. Pozo-Vzquez; Y. Castro-Dez (International Journal of Climatology, 2000)

Coat protein sequence comparisons of three Mexican isolates of papaya ringspot virus with other geographical isolates reveal a close relationship to American and Australian isolates - L. Silva-Rosales; N. Becerra-Leor; S. Ruiz-Castro; D. Téliz-Ortiz; J. C. Noa-Carrazana (Archives of Virology, 2000)

A high incidence of Shigella -induced arthritis in a primate species: major histocompatibility complex class I molecules associated with resistance and susceptiblity, and their relationship to HLA-B27 - J. A. Urvater; S. N. McAdam; J. H. Loehrke; T. M. Allen; J. L. Moran; T. J. Rowell; S. Rojo; J.A. López de Castro; J. D. Taurog; D. I. Watkins (Immunogenetics, 2000)

Reef coral reproduction in the Abrolhos Reef Complex, Brazil: the endemic genus Mussismilia - D. O. Pires; C. B. Castro; C. C. Ratto (Marine Biology, 1999)

Adenoviruses Encoding HPRT Correct Biochemical Abnormalities of HPRT-Deficient Cells and Allow Their Survival in Negative Selection Medium - Thomas D. Southgate; Derek Bain; Lynette D. Fairbanks; Adrian E. Morelli; Adriana T. Larregina; H. Anne Simmonds; Maria G. Castro; Pedro R. Löwenstein (Metabolic Brain Disease, 1999)

A 500-year precipitation record in Southern Spain - F.S. Rodrigo; M.J. Esteban-Parra; D. Pozo-Vázquez; Y. Castro-Díez (International Journal of Climatology, 1999)

Acid Phosphatase Polymorphism in European Shad (Fish: Clupeids) - F. Castro; D. Linhares; P. Alexandrino (Biochemical Genetics, 1999)

Origin of peraluminous granites and granodiorites, Iberian massif, Spain: an experimental test of granite petrogenesis - Antonio Castro; Alberto E. Patiño Douce; L. Guillermo Corretgé; Jesús D. de la Rosa; Mohammed El-Biad; Hassan El-Hmidi (Contributions to Mineralogy and Petrology, 1999)

β-Tubulin accumulation and DNA synthesis are sequentially resumed in embryo organs of cucumber (Cucumis sativus L.) seeds during germination - Hai -Chun Jing; André A. M. van Lammeren; Renato D. de Castro; Raoul J. Bino; Henk W. M. Hilhorst; Steven P. C. Groot (Protoplasma, 1999)

Follow-up of mercury levels in fish, human hair and urine in the Madeira and Tapajós basins, Amazon, Brazil - O. Malm; J. R. D. Guimarães; M. B. Castro; W. R. Bastos; J. P. Viana; F. J. P. Branches; E. G. Silveira; W. C. Pfeiffer (Water, Air, & Soil Pollution, 1997)

Geographical distribution of B chromosomes in the grasshopper Eyprepocnemis plorans, along a river basin, is mainly shaped by non-selective historical events - J. Cabrero; M. D. Lo´pez–Leo´n; R. Go´mez; A. J. Castro; A. Marti´–Alganza; J. P. M. Camacho (Chromosome Research, 1997)

A LIMITED-LENGTH-SCALE k-ε MODEL FOR THE NEUTRAL AND STABLY-STRATIFIED ATMOSPHERIC BOUNDARY LAYER - DAVID D. APSLEY; IAN P. CASTRO (Boundary-Layer Meteorology, 1997)

Antioxidative stress therapy with dithiothreitol tetraacetate I. Protection against carbon tetrachloride induced liver necrosis - M. M. de Mecca; G. D. Castro; J. A. Castro (Archives of Toxicology, 1993)

Late preventive effects of quinacrine on carbon tetrachloride induced liver necrosis - A. González Padrón; E. G. D. de Toranzo; J. A. Castro (Archives of Toxicology, 1993)

Interaction of trichloromethyl radicals with phenylalanine - Gerardo D. Castro; María I. Díaz Gómez; José A. Castro (Archives of Toxicology, 1991)

A diagnostic method to detect alcelaphine herpesvirus-1 of malignant catarrhal fever using the polymerase chain reaction - D. Hsu; L. M. Shih; A. E. Castro; Y. C. Zee (Archives of Virology, 1990)

Evidence for hydroxyl free radical formation during paraquat but not for nifurtimox liver microsomal biotransformation. A dimethyl-sulfoxide scavenging study - G. D. Castro; A. Lopez; J. A. Castro (Archives of Toxicology, 1988)

Early biochemical changes produced by malathion on toad embryos - E. A. Rosenbaum; A. Caballero de Castro; L. Gauna; A. M. Pechen de D'Angelo (Archives of Environmental Contamination and Toxicology, 1988)

Cholinesterase activities in developing amphibian embryos following exposure to the insecticides dieldrin and malathion - Monica C. de Llamas; Adriana C. de Castro; Ana M. Pechen de D'Angelo (Archives of Environmental Contamination and Toxicology, 1985)

African swine fever virus - R. C. Wardley; C. de M. Andrade; D. N. Black; F. L. de Castro Portugal; L. Enjuanes; W. R. Hess; C. Mebus; A. Ordas; D. Rutili; J. Sanchez Vizcaino; J. D. Vigario; P. J. Wilkinson; et al. (Archives of Virology, 1983)

The effect of nitrogen fertilization on the composition of the free amino acid pool of poato tubers - J. E. Hoff; C. M. Jones; G. E. Wilcox; Marlene D. Castro (American Journal of Potato Research, 1971)